Resin composition, molded article, and method for producing resin composition
By using technical means such as X-ray computed tomography and scanning electron microscopy in the resin composition, combined with the use of compatibilizers and processing aids, the good dispersion of natural fibers is achieved, and the problem of insufficient mechanical properties of the molded body in the prior art is solved, and the bending and tensile characteristics of the molded body are significantly improved.
Patent Information
- Application Number
- CN202380066037.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-20
- Filing Date
- 2023-08-28
- Publication Date
- 2025-04-29
AI Technical Summary
The prior art is difficult to fully disperse natural fibers in the resin, resulting in the inability to fully improve the bending and tensile characteristics of the molded body.
By using technical means such as X-ray computed tomography and scanning electron microscopy in the resin composition, the average fiber length and dispersion density of natural fibers are controlled, and combined with the use of compatibilizers and processing aids, the good dispersion of natural fibers and the full mixing of thermoplastic resins are achieved.
The dispersion of natural fibers in the resin composition is significantly improved, the bending strength, bending elastic modulus, tensile strength and tensile elastic modulus of the molded body are enhanced, and the mechanical properties of the molded body are improved.
Smart Images

Figure CN119907832A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a resin composition, a molded body, and a method for producing the resin composition. Background Art
[0002] Resins are lightweight and easy to shape, so they are widely used in various applications. Resins generally have lower mechanical strength (tensile properties, bending properties, impact resistance, etc.) than metals, so fillers are often added to improve mechanical strength.
[0003] As fillers, reinforcing fibers such as natural fibers, glass fibers, and carbon fibers are used. Among them, natural fibers such as cellulose are inexpensive and have little impact on the environment when discarded, so they have received particular attention in recent years.
[0004] For example, Patent Document 1 describes a cellulose composite material obtained by dispersing wood pulp (cellulose) in a polymer matrix. Patent Document 1 describes that pulp having a high water content is mixed with a polymer matrix using a twin-screw extruder to obtain pellets having high dispersibility of the pulp. Patent Document 1 also describes that the pellets can be used for injection molding and the like.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application No. 2019-512591 Summary of the invention
[0008] Problems to be solved by the invention
[0009] As described in Patent Document 1, it is believed that if natural fibers such as cellulose are well dispersed in a resin, a molded body having good mechanical properties such as bending properties (bending strength, bending elastic modulus) and tensile properties (tensile strength, tensile elastic modulus) can be obtained. However, according to the research of the inventors of the present application, even if natural fibers are dispersed by the method described in Patent Document 1, a molded body having sufficiently improved bending properties and tensile properties cannot be obtained.
[0010] In view of the above situation, the object of the present invention is to provide a resin composition in which natural fibers are dispersed in a resin, a molded body obtained from the resin composition, and a method for manufacturing the resin composition, wherein the resin composition can obtain a molded body having improved bending properties (bending strength, bending elastic modulus) and tensile properties (tensile strength, tensile elastic modulus).
[0011] Means for solving problems
[0012] One embodiment of the present invention relates to the resin compositions of the following [1] to
[12] .
[0013] [1] A resin composition comprising:
[0014] Thermoplastic resin (A), and
[0015] Natural fiber (B),
[0016] The average fiber length of the natural fiber (B), measured by photographing the resin composition using X-ray computed tomography (X-ray CT), is 32 μm or longer.
[0017] The ratio (number / average size) of the number of the natural fibers (B) in the image obtained by photographing and measuring the cross section along the TD direction of the resin composition using a scanning electron microscope (SEM), in which the range of 1.8 mm×1.2 mm was photographed at a working distance of 6.5 mm and a magnification of 75 times, relative to the average size (μm) of the natural fibers (B) is 400 or more.
[0018] [2] A resin composition as described in [1], wherein the ratio (number / area) of the number of the natural fibers (B) in an image obtained by photographing and measuring a cross section along the TD direction of the resin composition using a SEM, wherein the image is taken at a working distance of 6.5 mm and a magnification of 75 times over a range of 1.8 mm×1.2 mm, relative to the area (%) occupied by the natural fibers (B) is 700 or more.
[0019] [3] The resin composition according to [1] or [2], wherein the ratio of the total mass of the natural fiber (B) to the total mass of the thermoplastic resin (A) ((B) / (A)) is 0.01 to 10.
[0020] [4] The resin composition as described in any one of [1] to [3], wherein the ratio of the total mass of the natural fiber (B) to the total mass of the thermoplastic resin (A) and the natural fiber (B) ((B) / ((A)+(B))) is 0.50 or more.
[0021] [5] The resin composition according to any one of [1] to [4], comprising a compatibilizer (C), wherein the compatibilizer (C) comprises a modified polyolefin (C1).
[0022] [6] The resin composition according to [5], wherein the modified polyolefin (C1) is an acid-modified polyolefin resin composition.
[0023] [7] A resin composition as described in [5] or [6], wherein the ratio of the total mass of the aforementioned compatibilizer (C) to the total mass of the aforementioned thermoplastic resin (A), the aforementioned natural fiber (B) and the aforementioned compatibilizer (C) ((C) / ((A)+(B)+(C))) is greater than or equal to 0.008 and less than or equal to 0.1.
[0024] [8] The resin composition according to any one of [1] to [7], comprising a processing aid (D), wherein the processing aid (D) comprises a polyolefin wax (D1).
[0025] [9] The resin composition according to any one of [1] to [8], wherein the natural fiber (B) comprises cellulose fiber.
[0026]
[10] The resin composition described in [9], wherein the maximum fiber length of the natural fiber (B) measured by photographing the resin composition using X-ray computed tomography (X-ray CT) is 900 μm or less.
[0027]
[11] The resin composition according to any one of [1] to
[10] , wherein the thermoplastic resin (A) comprises a polyolefin.
[0028]
[12] The resin composition according to any one of [1] to
[11] , wherein the ratio ((A) / (W)) of the total mass of the thermoplastic resin (A) to the total mass (W) of the resin composition is 0.5 or less.
[0029] Another aspect of the present invention relates to the molded article of the following
[13] .
[0030]
[13] A molded article formed by injection molding the resin composition according to any one of [1] to
[12] .
[0031] Another aspect of the present invention relates to a method for producing a resin composition according to the following
[14] .
[0032]
[14] The method for producing a resin composition according to any one of [1] to
[12] , wherein:
[0033] The thermoplastic resin (A) and the natural fiber (B) are melt-kneaded using a batch-type closed kneading device having a housing and a rotor with stirring blades, and
[0034] The melt kneading is performed by heating the temperature inside the housing to a temperature at which the natural fibers (B) are not denatured by the rotation of the rotor in the presence of water.
[0035] Effects of the Invention
[0036] According to the present invention, a resin composition in which natural fibers are dispersed in a resin, a molded body obtained from the resin composition, and a method for manufacturing the resin composition can be provided, wherein the resin composition can obtain a molded body having improved bending properties (bending strength, bending elastic modulus) and tensile properties (tensile strength, tensile elastic modulus). BRIEF DESCRIPTION OF THE DRAWINGS
[0037] [ Figure 1 ] Figure 1 This is an X-ray CT image of an injection-molded body obtained from the resin composition 1 obtained in Example.
[0038] [ Figure 2 ] Figure 2 A is a SEM image of the TD cross section of an injection molded body obtained from the resin composition 1 obtained in Example, Figure 2 B is due to Figure 2 A obtained secondary image.
[0039] [ Figure 3 ] Figure 3 This is a SEM image of the resin composition 2 obtained in Example. DETAILED DESCRIPTION
[0040] 1. Resin composition
[0041] A first embodiment of the present invention relates to a resin composition including a thermoplastic resin (A) and a natural fiber (B).
[0042] For the above-mentioned resin composition, the average fiber length of the natural fiber (B) measured by X-ray computed tomography (X-ray CT) is 32 μm or more (hereinafter referred to as "Condition 1"). In addition, for the above-mentioned resin composition, the ratio (number / average size) of the number of natural fibers (B) in the image obtained by photographing and measuring the cross section along the TD direction with a scanning electron microscope (SEM) at a working distance of 6.5 mm (the distance between the objective lens and the surface of the test piece for measurement) and a magnification of 75 times over a range of 1.8 mm × 1.2 mm relative to the average size (μm) of the natural fibers (B) is 400 or more (hereinafter referred to as "Condition 2").
[0043] In addition, for the above-mentioned resin composition, the ratio (number / area) of the number of natural fibers (B) in the image obtained by photographing and measuring the cross-section along the TD direction with a scanning electron microscope (SEM) at a working distance of 6.5 mm and a magnification of 75 times over a range of 1.8 mm×1.2 mm to the area (%) occupied by the natural fibers (B) is preferably 700 or more (hereinafter also referred to as "Condition 3").
[0044] In the resin composition satisfying condition 1, the natural fiber (B) is dispersed while being relatively long. Therefore, the effect of improving the flexural properties (flexural strength, flexural modulus) and tensile properties (tensile strength, tensile modulus) by the natural fiber (B) can be more fully achieved.
[0045] From the above viewpoint, the average fiber length of the natural fiber (B) photographed and measured by X-ray CT is preferably 34 μm or more, more preferably 36 μm or more, and further preferably 38 μm or more. The upper limit of the average fiber length of the above-mentioned natural fiber (B) is not particularly limited, and can be set to less than 100 μm, or less than 90 μm. In addition, from the viewpoint of more fully realizing the effect of improving the bending properties and tensile properties brought by the natural fiber (B), the above-mentioned resin composition is preferably included in the natural fiber (B) having a fiber length of more than 150 μm when photographed and measured by X-ray CT.
[0046] In addition, from the viewpoint of more fully realizing the effect of improving the bending properties and tensile properties brought by the natural fiber (B) and making the surface appearance of the resin composition better, the maximum fiber length of the natural fiber (B) photographed and measured by X-ray computed tomography (X-ray CT) is preferably 900 μm or less, more preferably 800 μm or less, further preferably 600 μm or less, and particularly preferably 500 μm or less. The lower limit of the maximum fiber length of the natural fiber (B) is not particularly limited, for example, it can be more than 100 μm, or it can be more than 150 μm. That is, the maximum fiber length of the natural fiber (B) is preferably more than 100 μm and less than 900 μm, more preferably more than 100 μm and less than 800 μm, further preferably more than 150 μm and less than 600 μm, and particularly preferably more than 150 μm and less than 500 μm.
[0047] X-ray CT imaging for measuring the average fiber length was performed under the following conditions.
[0048] An arbitrary part of the test piece for measurement was cut into 1mm×1mm×2mm, and X-ray CT was taken with a field of view of about 3mm×3mm. The measurement device used a high-resolution 3D X-ray microscope nano3DX (manufactured by Rigaku Corporation), and CT measurement was performed using low-energy, high-brightness X-rays that can obtain contrast even for light elements. The detailed measurement conditions are as follows.
[0049]
[0050] For the resin combination satisfying condition 2, the average size of the natural fiber (B) in the cross section (TD cross section) in the direction perpendicular to the flow direction of the resin combination during manufacture is small, and the number is large. When manufacturing the resin combination, the natural fiber (B) is oriented to a certain extent in the flow direction of the resin combination, and therefore, the average size of the natural fiber (B) in the TD cross section becomes the value reflecting the average diameter of the natural fiber (B) in the resin combination to a certain extent. Therefore, in the resin combination satisfying condition 2, the natural fiber (B) is finely and finely micro-dispersed, and it can be said that its dispersibility is high. Therefore, the resin combination satisfying condition 2 is not easy to produce the improvement of the mechanical strength caused by the uneven dispersion of the natural fiber (B) in its molded body, and the improvement effect of the bending properties (bending strength, bending elastic modulus) and the tensile properties (tensile strength, tensile elastic modulus) brought by the natural fiber (B) can be more fully realized.
[0051] From the above viewpoints, the ratio of the number of natural fibers (B) to the average size (μm) of the natural fibers (B) in the SEM image of the TD cross section is preferably 450 or more, more preferably 480 or more, further preferably 600 or more, and particularly preferably 750 or more. The upper limit of the above ratio is not particularly limited, and can be set to 2000 or less, or 1500 or less.
[0052] For the resin composition satisfying condition 3, the number of natural fibers (B) in the cross section (TD cross section) in the direction perpendicular to the flow direction of the resin composition during manufacture relative to the area occupied by natural fibers (B) (that is, the amount (volume) of natural fibers) is large. Therefore, in the resin composition satisfying condition 3, the natural fibers (B) are finely and finely dispersed, and it can be said that their dispersibility is high. Therefore, the resin composition satisfying condition 3 is not easy to produce the insufficient improvement of mechanical strength caused by the uneven dispersion of natural fibers (B) in its molded body, and the improvement effect of the bending properties (bending strength, bending elastic modulus) and tensile properties (tensile strength, tensile elastic modulus) brought by natural fibers (B) can be more fully realized.
[0053] From the above viewpoints, the ratio of the number of natural fibers (B) to the area (%) occupied by natural fibers (B) in the SEM image of the TD cross section is preferably 750 or more, more preferably 800 or more, and further preferably 950 or more. The upper limit of the above ratio is not particularly limited, and can be set to 2000 or less, or 1800 or less.
[0054] It should be noted that in the SEM image obtained by photographing the above-mentioned TD cross section using SEM, the natural fiber (B) appears to be granular. Moreover, the so-called average size of the natural fiber (B) is the average value of the area of each of the granular natural fibers (B). In addition, the so-called number of natural fibers (B) is the number of the granular natural fibers. In addition, the area (%) occupied by the so-called natural fiber (B) is the ratio ((Sc / St)×100) of the area (Sc) occupied by the granular natural fiber (B) relative to the total area (St) of the SEM image.
[0055] The above-mentioned TD cross section was photographed by SEM under the following conditions.
[0056] For any TD cross section of the test piece for measurement, within the range of 1.8mm×1.2mm, a high-resolution scanning microscope (SEM) was used, the working distance was set to 6.5mm, and the image was magnified to 75 times for observation. The area filled with natural fibers (B) in the enlarged image obtained by observation was painted black and the other areas were painted white to make a secondary image. The obtained secondary image was read into the image analysis software (ImageJ), and the instructions: Process, Binary, MakeBinary were used to perform binary image processing, and the average size of natural fibers (B) in the area of the observation field (Average Size of black area), the number of natural fibers (B) (Count of black area), and the area % of natural fibers (B) (Area Fraction of black area) were calculated by the instructions: Analyze, Analyze Particles.
[0057] It should be noted that the hydrophilic tendency of natural fiber (B) is usually strong, and it is difficult to disperse into a substantially hydrophobic resin. Especially in a low polarity resin such as polyolefin and polystyrene, natural fiber (B) is very difficult to disperse. Therefore, in a conventional method such as the method described in patent document 1, if natural fiber (B) is to be fully dispersed, very strong mixing is required. Moreover, by this mixing, natural fiber (B) is also cut off in the length direction (becoming unsatisfied with condition 1), and the bending properties and tensile properties of the molded body are difficult to fully improve. On the other hand, if the intensity of mixing is reduced in order to prevent the cutting of natural fiber (B), natural fiber (B) cannot be fully dispersed, and the bending properties and tensile properties of the molded body are still difficult to fully improve.
[0058] In contrast, in the present embodiment, by adjusting the dispersion method of the natural fiber (B), the natural fiber (B) is well dispersed in the cross-sectional direction, and the cutting in the length direction is suppressed. Moreover, a resin combination satisfying condition 1 and condition 2, and further preferably condition 3 can be obtained. Hereinafter, the materials included in the resin combination and its molded body are first described, and the dispersion method of the natural fiber (B) is described later.
[0059] It should be noted that the above characteristics of the length and distribution of the natural fiber (B) possessed by the resin composition will also be inherited by the molded body (e.g., injection molded body). Conversely, if the length and distribution of the natural fiber (B) measured for the molded body meet the above characteristics, it can be inferred that the resin composition used to manufacture the molded body also has the same characteristics.
[0060] The resin composition and the molded article contain a thermoplastic resin (A) and a natural fiber (B). The resin composition may further contain a compatibilizer (C), a processing aid (D), and other optional components.
[0061] 1-1. Thermoplastic resin (A)
[0062] The type of thermoplastic resin (A) is not particularly limited. For example, thermoplastic resins described in "Practical Plastic Dictionary" (edited by Practical Plastic Dictionary Editorial Committee, Industrial Research Institute Co., Ltd.) can be widely used. The thermoplastic resin (A) may include only one type or two or more types. It should be noted that the thermoplastic resin (A) can also be produced using raw materials from biomass.
[0063] Examples of thermoplastic resins (A) include polyolefins, polyamides, polyesters, polyacetals, styrene (co)polymers, acrylic resins, polycarbonates, polyphenylene ethers, polyvinyl chloride, chlorine resins such as polyvinylidene chloride, vinyl acetate resins, ethylene-(meth)acrylate copolymers, ethylene-acrylic acid copolymers, ethylene-methacrylic acid copolymers or ionomers thereof, vinyl alcohol resins, thermoplastic urethane elastomers, and rubber components, etc. Among them, polyolefins are preferred.
[0064] Examples of polyolefins include olefin homopolymers such as polyethylene, polypropylene, poly-1-butene, and polymethylbutene, and olefin copolymers such as ethylene-α-olefin random copolymers, propylene-ethylene random copolymers, and ethylene·α-olefin·non-conjugated polyene copolymers. Among them, polyethylene and polypropylene are preferred, and polypropylene is more preferred from the viewpoint of improving the heat resistance and rigidity of the molded body. It should be noted that the types and proportions of the structural units constituting the various polyolefins can be determined by 13 C-NMR was used to determine.
[0065] The polyolefin may be, for example, an ethylene polymer. The ethylene polymer is preferably an ethylene homopolymer or a copolymer of ethylene and an α-olefin having a carbon number of 3 or more and 12 or less. Specific examples of ethylene homopolymers include ultra-high molecular weight polyethylene, high density polyethylene, medium density polyethylene, low density polyethylene, linear low density polyethylene, etc.
[0066] On the other hand, when the ethylene polymer is a copolymer of ethylene and an alpha-olefin having more than 3 carbon atoms and less than 12 carbon atoms, the ratio of the structural unit derived from ethylene is preferably more than 91.0 mol % and less than 99.9 mol %. On the other hand, the ratio of the structural unit derived from the alpha-olefin having more than 3 carbon atoms is preferably more than 0.1 mol % and less than 9.0 mol % (the total amount of the structural unit derived from ethylene and the structural unit derived from the alpha-olefin having more than 3 carbon atoms is set to 100 mol %).
[0067] Examples of the α-olefins having 3 to 12 carbon atoms include linear or branched α-olefins such as propylene, 1-butene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, 3-methyl-1-pentene, 1-octene, 1-decene, and 1-dodecene. By preparing a copolymer of ethylene and an α-olefin having 3 to 12 carbon atoms, the moldability, appearance, and mechanical strength of the molded body become good. It should be noted that the structural units derived from these α-olefins may include only one or more.
[0068] The polyolefin may be a propylene homopolymer (polypropylene), or a propylene-based polymer of propylene and ethylene or an α-olefin having 4 to 12 carbon atoms.
[0069] When making the propylene-based polymer a copolymer of propylene and ethylene, the ratio of the structural unit derived from propylene can be set to more than 60 mol % and less than 99.5 mol % (the total amount of the structural unit derived from propylene and the structural unit derived from ethylene is set to 100 mol %). If a propylene-based polymer with a large ratio of structural units derived from propylene is used, the moldability, appearance, and heat resistance of the molded article become good.
[0070] In the case where the propylene polymer is a copolymer of propylene and an α-olefin having a carbon number of 4 or more and 12 or less, examples of α-olefins having a carbon number of 4 or more and 12 or less include linear or branched α-olefins such as 1-butene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, 3-methyl-1-pentene, 1-octene, 1-decene, and 1-dodecene. Among them, 1-butene is preferred. In addition, the propylene α-olefin copolymer at this time may also contain olefins other than α-olefins having a carbon number of 4 or more and 12 or less, for example, a structural unit derived from ethylene or the like may be contained in a small amount, for example, in an amount of 10 mol% or less. On the other hand, from the viewpoint of improving the balance between the heat resistance and mechanical strength of the molded body, it is also preferred not to contain a structural unit derived from ethylene. It should be noted that the structural units derived from these α-olefins may contain only one kind or may contain two or more kinds.
[0071] When the propylene polymer is a copolymer of propylene and an α-olefin having 4 to 12 carbon atoms, the ratio of the structural unit derived from propylene is preferably 60 mol% to 90 mol%. On the other hand, the ratio of the structural unit derived from the α-olefin having 4 to 12 carbon atoms is preferably 10 mol% to 40 mol% (the total amount of the structural unit derived from propylene and the structural unit derived from the α-olefin having 4 to 12 carbon atoms is set to 100 mol%).
[0072] When the composition of the propylene·α-olefin copolymer is within the above range, the appearance, mechanical strength and heat resistance of the molded article are improved. In particular, the appearance of the molded article is improved, probably because the crystallization rate is slow, so the resin composition can flow in the mold for a longer time.
[0073] The melting point (Tm) of the propylene / α-olefin copolymer as measured by DSC is usually 60°C to 120°C, preferably 65°C to 100°C.
[0074] The polyolefin may be an ethylene·α-olefin·non-conjugated polyene copolymer. The copolymer is preferably a copolymer of ethylene, an α-olefin having a carbon number of 3 or more and 12 or less and a non-conjugated polyene, and more preferably a copolymer obtained by random copolymerization of them. Examples of the α-olefin include α-olefins having a carbon number of 3 or more and 12 or less, such as propylene, 1-butene, 1-pentene, 3-methyl-1-butene, 1-hexene, 3-methyl-1-pentene, 1-octene, 1-decene, and 1-dodecene, etc., which are linear or branched α-olefins having a carbon number of 3 or more and 12 or less. Examples of the non-conjugated polyene include cyclic or chain non-conjugated polyenes. Examples of cyclic non-conjugated polyenes include cyclopentene, cycloheptene, norbornene, 5-ethylidene-2-norbornene, dicyclopentadiene, 5-vinyl-2-norbornene, norbornadiene, methyltetrahydroindene, and tetracyclododecene. Examples of chain non-conjugated polyenes include 1,4-hexadiene, 7-methyl-1,6-octadiene, 4-ethylidene-8-methyl-1,7-nonadiene, and 4-ethylidene-1,7-undecadiene. Among them, preferably 5-ethylidene-2-norbornene, dicyclopentadiene, and 5-vinyl-2-norbornene. It should be noted that the structural units derived from these non-conjugated polyenes may include only one kind or two or more kinds.
[0075] Examples of the above-mentioned ethylene·α-olefin·non-conjugated polyene random copolymer include ethylene·propylene·diene terpolymer (EPDM) and the like.
[0076] Moreover, as the polyolefin, a propylene·α-olefin·non-conjugated polyene copolymer, a 1-butene·α-olefin·non-conjugated polyene copolymer, or the like can also be used.
[0077] Moreover, as polyolefin, known ethylene / cyclic olefin copolymer (COC) and cyclic olefin polymer (COP) can also be used.
[0078] 1-2. Natural fiber (B)
[0079] Examples of natural fibers (B) include wood flour (a material obtained by processing the skin of wood using a crusher), wood fiber, bamboo powder, bamboo fiber, cellulose fiber obtained by separation, wool, agricultural fiber, wood pulp (a pulp made of wood as a raw material, and obtained by mechanically treating, chemically treating or compositely treating a material obtained by removing the bark of a tree trunk and directly flaking it), other natural pulps, rayon, cotton, etc. Examples of the above-mentioned agricultural fiber include wheat straw, rice straw, hemp, flax, kenaf, kapok, jute, ramie, sisal, Henaquin fiber, corn fiber, coconut shell fiber, nut shell, and rice bran, etc. Examples of the above-mentioned wood pulp include NBKP (bleached coniferous wood pulp) and LBKP (bleached kraft pulp of broadleaf trees), etc. Examples of the above-mentioned other natural pulps include Manila hemp, paper mulberry, jasmine, and goose skin, etc. Among them, wood powder, wood fiber, bamboo, bamboo fiber, cotton, and cellulose fibers obtained by separation are preferred. From the viewpoint of suppressing the deviation of the mechanical strength of the molded body and improving the predictability of the strength of the obtained molded body, cellulose fibers obtained by separation are more preferred.
[0080] The source of the above-mentioned cellulose fiber is not particularly limited, and can be cellulose fiber obtained from any material such as tree, grass, pulp, and paper. The cellulose fiber obtained from tree can be cellulose fiber obtained from any wood raw material in conifers and broad-leaved trees. The cellulose fiber obtained from grass can be cellulose fiber obtained from non-wood raw materials such as Gramineae, Malvaceae, Leguminosae, and Palmaceae. The cellulose fiber obtained from pulp can be cellulose fiber obtained from any pulp such as cotton linter pulp obtained from the fibers around cotton seeds. The cellulose fiber obtained from paper can be cellulose fiber obtained from any paper such as newspapers, corrugated paper, magazines, and high-grade paper. Among them, from the perspective of being easy to obtain and cheap, it is preferably cellulose fiber obtained from trees or grasses, and more preferably cellulose fiber obtained from trees.
[0081] From the viewpoint of improving the mechanical strength and impact resistance of the molded article, the average degree of polymerization of the cellulose fibers is preferably from 50 to 2000, more preferably from 100 to 1500. The average degree of polymerization of the cellulose fibers can be measured by the reduced specific viscosity method using a copper ethylenediamine solution as described in the confirmation test (3) of the "Explanation of the 15th Revised Edition of the Japanese Pharmacopoeia (published by Hirokawa Shoten)".
[0082] The cellulose fibers may be unmodified or amorphized cellulose fibers, modified cellulose fibers, or amorphized cellulose fibers. The modified cellulose fibers may be cellulose fibers obtained by reacting hydroxyl groups of cellulose with ether compounds, alkyl chlorides, alkyl acid anhydrides, alkyl acid chlorides, etc. The amorphized cellulose fibers may be cellulose fibers obtained by reducing the crystallinity of cellulose using a known method.
[0083] The cellulose fibers have hydroxyl groups and polar functional groups such as hydroxyl groups, carboxyl groups, amino groups, and quaternary ammonium groups introduced by modification.
[0084] Examples of commercially available products of the cellulose fibers include KC FLOCK GK series ("KC FLOCK" is a registered trademark of the company), which is powdered cellulose manufactured by Nippon Paper Industries, Ltd.
[0085] 1-3. Compatibilizer (C)
[0086] The compatibilizer (C) improves the compatibility between the thermoplastic resin (A) and the natural fiber (B). The compatibilizer improves their compatibility and facilitates the fine dispersion of the natural fiber (B), thereby improving the processability, heat resistance, mechanical strength, and appearance of the molded product.
[0087] When the amount of natural fiber (B) added is high or the surface area of natural fiber (B) is large (when natural fiber (B) is thin), thermoplastic resin (A) and natural fiber (B) may not be compatible. In this case, the effect of improving their compatibility by using compatibilizer (C) and thus improving the microdispersibility of natural fiber (B) is significant. In addition, by adding compatibilizer (C), Figure 3 Thus, the thermoplastic resin (A) and the natural fiber (B) are closely attached to each other, and therefore, it is considered that not only the mechanical strength but also the appearance is improved.
[0088] The compatibilizer (C) comprises a modified polyolefin (C1) or a petroleum resin (C2). According to the new insights of the inventors of the present application, it is believed that these compatibilizers (C) having polar functional groups such as oxygen atoms or cyclic structures such as styrene in the molecular chain have high affinity with natural fibers (B) having a cellulose skeleton as a cyclic structure containing oxygen atoms, and are easily locally present on the surface of the natural fibers (B). Therefore, it is believed that by using these compatibilizers (C) having good compatibility with the thermoplastic resin (A) and high affinity with the natural fibers (B), the effect of improving the microdispersibility of the natural fibers (B) can be significantly achieved.
[0089] (1) Modified polyolefin (C1)
[0090] The modified polyolefin (C1) may be an unsaturated carboxylic acid modified product of a polyolefin, a styrene modified product, an air oxide, etc. These modified polyolefins (C1) can be obtained by modifying an unmodified polyolefin using a known method. It should be noted that the modified polyolefin (C1) can also be produced using raw materials from biomass.
[0091] (Polyolefins used as raw materials)
[0092] The type of polyolefin (unmodified polyolefin) used as a raw material of the modified polyolefin is not particularly limited. The unmodified polyolefin may be, for example, a homopolymer or copolymer of an α-olefin such as ethylene, propylene, 1-butene, 1-pentene, 2-methyl-1-butene, 3-methyl-1-butene, 1-hexene, 3-methyl-1-pentene, 4-methyl-1-pentene, 3,3-dimethyl-1-butene, 1-heptene, methyl-1-hexene, dimethyl-1-pentene, trimethyl-1-butene, ethyl-1-pentene, 1-octene, methyl-1-pentene, dimethyl-1-hexene, trimethyl-1-pentene, ethyl-1-hexene, methyl-1-ethylpentene, diethyl-1-butene, propyl-1-pentene, 1-decene, methyl-1-nonene, dimethyl-1-octene, trimethyl-1-heptene, ethyl-1-octene, methylethyl-1-heptene, diethyl-1-hexene, 1-dodecene, and 1-hexadecene. These α-olefins may be selected based on their compatibility with the thermoplastic resin (A). For example, when the thermoplastic resin (A) is a polyolefin (A-1), it is preferably a resin of the same type as the polyolefin (A-1) (when the polyolefin (A-1) is polyethylene, the unmodified polyolefin is also polyethylene, and when the polyolefin (A-1) is polypropylene, the unmodified polyolefin is also polypropylene. For example, the unmodified polyolefin is preferably a polypropylene, especially a homopolymer of propylene, a propylene·ethylene random copolymer, and a propylene·1-butene random polymer.
[0093] (Unsaturated carboxylic acid-modified unmodified polyolefin)
[0094] The unsaturated carboxylic acid used in the modification of the unmodified polyolefin may be an unsaturated compound having one or more carboxylic acid groups (unsaturated carboxylic acid in a narrow sense), or may be an ester of an unsaturated carboxylic acid with an alkyl alcohol, an unsaturated carboxylic acid anhydride, or other unsaturated carboxylic acid derivatives such as unsaturated compounds having carboxylic acid anhydride. The unsaturated groups possessed by these unsaturated carboxylic acids may be vinyl, vinylidene, and unsaturated cyclic hydrocarbon groups, etc. Examples of unsaturated carboxylic acids in a narrow sense include acrylic acid, methacrylic acid, maleic acid, fumaric acid, tetrahydrophthalic acid, itaconic acid, citraconic acid, crotonic acid, nadic acid, and endo-cis-bicyclo[2,2,1]hept-5-ene-2,3-dicarboxylic acid, etc. Examples of derivatives of unsaturated carboxylic acids include anhydrides such as maleic anhydride and citraconic anhydride, and acyl halides, amides, imides, and esters of unsaturated carboxylic acids (in a narrow sense) such as maleic chloride, maleimide, monomethyl maleate, and dimethyl maleate. The unsaturated carboxylic acid is preferably maleic acid, nadic acid or anhydrides thereof, and more preferably maleic anhydride. These unsaturated carboxylic acids may be used alone or in combination of two or more.
[0095] When unmodified polyolefin is modified by using these unsaturated carboxylic acids, an organic peroxide can be used as a free radical initiator. Examples of the above-mentioned organic peroxides include di-n-propyl peroxydicarbonate, diisopropyl peroxydicarbonate, di-sec-butyl peroxydicarbonate, tert-hexyl peroxyneodecanoate, tert-butyl peroxyneodecanoate, tert-amyl peroxyneodecanoate, tert-butyl peroxyneoheptanoate, tert-hexyl peroxypivalate, tert-butyl peroxypivalate, tert-amyl peroxypivalate, tert-hexyl peroxy-2-ethylhexanoate, tert-butyl peroxy-2-ethylhexanoate, tert-amyl peroxy-2-ethylhexanoate, tert-butyl peroxy-isobutyrate, 1,1-di(tert-butylperoxy)-2-methyl Cyclohexane, 1,1-di(tert-hexylperoxy)-3,3,5-trimethylcyclohexane, 1,1-di(tert-hexylperoxy)cyclohexane, 1,1-di(tert-butylperoxy)cyclohexane, 1,1-di(tert-amylperoxy)cyclohexane, 2,2-di(4,4-di-(tert-butylperoxy)cyclohexyl)propane, tert-amyl peroxyisononanoate, tert-hexyl peroxyisopropyl monocarbonate, tert-amyl peroxyoctanoate, tert-butyl peroxymaleate, tert-butyl peroxy-3,5,5-trimethylhexanoate, tert-butyl peroxylaurate, isopropyl peroxide tert-Amyl monocarbonate, tert-butyl peroxyisopropyl monocarbonate, tert-Amyl peroxy-2-ethylhexyl monocarbonate, tert-butyl peroxy-2-ethylhexyl monocarbonate, tert-Hexyl peroxybenzoate, tert-Butyl peroxyacetate, tert-Amyl peroxyacetate, 2,2-Di-(tert-Butylperoxy)butane, tert-Butyl peroxyisononanoate, tert-Amyl peroxybenzoate, tert-Butyl peroxybenzoate, 4,4-Di-(tert-Butylperoxy)valerate, methyl ethyl ketone peroxide, di(2-tert-Butylperoxyisopropyl)benzene, 3,3-Di(tert-Butylperoxy)butane ) ethyl butyrate, di-tert-hexyl peroxide, 1,3-bis(2-tert-butyl peroxyisopropyl)benzene, 2,5-dimethyl-2,5-bis-(tert-butyl peroxide)hexane, tert-butyl cumyl peroxide, di-tert-amyl peroxide, di-tert-butyl peroxide, 2,5-dimethyl-2,5-bis-(tert-butyl peroxide)hex-3-yne, tert-amyl hydroperoxide, tert-butyl hydroperoxide, 1,1-bis(tert-butyl peroxide)-3,3,5-trimethylcyclohexane, and 1,1-bis(tert-butyl peroxide)-3,3,5-trimethylcyclohexane etc. Among them, preferably 2,5-dimethyl-2,5-bis-(tert-butyl peroxide)hexane, di-tert-butyl peroxide, peroxyisopropyl monocarbonate tert-butyl, and peroxybenzoic acid tert-butyl ester.These organic peroxy acids can use only one kind, and can also use more than two kinds.
[0096] The amount of the organic peroxide used for modification may be 0.01 to 30 parts by mass, preferably 1 to 20 parts by mass, and more preferably 2 to 15 parts by mass, based on 100 parts by mass of the unmodified polyolefin.
[0097] (Acid-modified polyolefin resin composition)
[0098] The unsaturated carboxylic acid modified product preferably becomes a composition containing the unsaturated carboxylic acid modified product of polyolefin and the unsaturated carboxylic acid in the resin composition and the molded body (hereinafter, also referred to as "acid-modified polyolefin resin composition"). That is, the resin composition and the molded body preferably contain the unsaturated carboxylic acid modified product of polyolefin and the unsaturated carboxylic acid. It should be noted that the unsaturated carboxylic acid contained in the acid-modified polyolefin resin composition may be the same unsaturated carboxylic acid as the unsaturated carboxylic acid used to modify the unmodified polyolefin, or may be an unsaturated carboxylic acid different from the unsaturated carboxylic acid.
[0099] From the viewpoint of further improving the bending and tensile properties of the obtained molded article, the unsaturated carboxylic acid contained in the acid-modified polyolefin resin composition preferably has a nonpolar group, and more preferably has a hydrocarbon group having 1 to 30 carbon atoms as the nonpolar group.
[0100] Examples of the hydrocarbon group having 1 to 30 carbon atoms include: a linear or branched alkyl group having 1 to 30 carbon atoms, preferably 1 to 20 carbon atoms, including methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, neopentyl, and n-hexyl; a linear or branched alkenyl group having 2 to 30 carbon atoms, preferably 2 to 20 carbon atoms, including vinyl, allyl, and isopropenyl; and a linear or branched alkynyl group having 2 to 30 carbon atoms, preferably 2 to 20 carbon atoms, including ethynyl and propargyl. Cyclic saturated hydrocarbon groups having 3 to 30 carbon atoms, preferably 3 to 20 carbon atoms, including cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, and adamantyl; cyclic unsaturated hydrocarbon groups having 5 to 30 carbon atoms, including cyclopentadienyl, indenyl, and fluorenyl; aryl groups having 6 to 30 carbon atoms, preferably 6 to 20 carbon atoms, including phenyl, benzyl, naphthyl, biphenyl, terphenyl, phenanthrenyl, and anthracenyl; alkyl-substituted aryl groups having 7 to 20 carbon atoms, including tolyl, isopropylphenyl, tert-butylphenyl, dimethylphenyl, and di-tert-butylphenyl. Among them, preferred are groups having an aromatic ring, such as aryl groups having 6 to 30 carbon atoms, preferably 6 to 20 carbon atoms, including phenyl, benzyl, naphthyl, biphenyl, terphenyl, phenanthrenyl, and anthracenyl, and alkyl-substituted aryl groups including tolyl, isopropylphenyl, tert-butylphenyl, dimethylphenyl, and di-tert-butylphenyl.
[0101] The molecular weight of the unsaturated carboxylic acid contained in the acid-modified polyolefin resin composition is preferably 1,000 or less, more preferably 500 or less, and particularly preferably 300 or less. As the unsaturated carboxylic acid having a hydrocarbon group with a carbon number of 1 to 30 and such a low molecular weight, benzyl succinic acid and benzyl succinic anhydride are preferred. It should be noted that the benzyl succinic acid derivative can be synthesized by a known method, for example, by a method described in Journal of Organic Chemistry ((Journal of Organic Chemistry) Vol. 21, p. 1473, 1956), or can be purchased and used as a commercial product.
[0102] The amount of unsaturated carboxylic acid contained in the acid-modified polyolefin resin composition is preferably 0.005 mass % to 10 mass %, more preferably 0.01 mass % to 5 mass %, further preferably 0.02 mass % to 3 mass %, based on the total mass of the acid-modified polyolefin resin composition.
[0103] The acid-modified polyolefin resin composition can be prepared by a method in which a part of the unsaturated carboxylic acid is kept unreacted and remains when synthesizing the unsaturated carboxylic acid modified product of the unmodified polyolefin (hereinafter, the preparation method is also referred to as "one-step method".), or by adding the unsaturated carboxylic acid after synthesizing the unsaturated carboxylic acid modified product (hereinafter, the preparation method is also referred to as "two-step method".). The one-step method can obtain the acid-modified polyolefin composition by a single-step process, and is cheap, so it is preferred. In addition, according to the one-step method, when unmodified polyolefin is modified by maleic anhydride, benzyl succinic acid or benzyl succinic anhydride is generated as a by-product, and an acid-modified polyolefin resin composition containing these by-products can also be obtained. On the other hand, when the unsaturated carboxylic acid used in the synthesis of the unsaturated carboxylic acid modified product of the unmodified polyolefin is different from the type of the unsaturated carboxylic acid contained in the acid-modified polyolefin resin composition, and when the control for limiting the homopolymerization of the unsaturated carboxylic acid becomes complicated, it is preferably a two-step method.
[0104] When the acid-modified polyolefin resin composition is prepared by a two-step method, the unsaturated carboxylic acid modified product of the unmodified polyolefin and the unsaturated carboxylic acid can be mixed using a Henschel mixer, a Banbury mixer, a V-type mixer, a tumble mixer, and a ribbon mixer, and then melt-kneaded at 160 to 300° C., preferably 180 to 250° C., using a single-screw extruder, a multi-screw extruder, a roll, and a kneader. During the mixing or melt-kneading, other additives can be added as needed. It should be noted that when synthesizing the unsaturated carboxylic acid modified product of the unmodified polyolefin, melt-kneading with the unsaturated carboxylic acid can be directly performed in situ.
[0105] (Modified polyolefin wax)
[0106] The modified polyolefin (C1) may be a modified product of a polyolefin wax. The modified product of a polyolefin wax may be an unsaturated carboxylic acid modified product, a styrene modified product, a sulfonic acid modified product, an air oxide, etc. of a polyolefin wax which is a homopolymer or copolymer of ethylene or an α-olefin having a carbon number of 3 or more and 12 or less. These modified products of polyolefin wax can be obtained by modifying an unmodified polyolefin wax using a known method.
[0107] The type of polyolefin wax (unmodified polyolefin wax) used as the raw material of the modified polyolefin wax is not particularly limited, but preferably includes ethylene homopolymer, propylene homopolymer, 4-methyl-1-pentene homopolymer, copolymer of ethylene and α-olefin having 3 to 12 carbon atoms, copolymer of propylene and ethylene or α-olefin having 4 to 12 carbon atoms, and copolymer of 4-methyl-1-pentene and other α-olefins. In the above copolymers, the monomer copolymerized with ethylene or propylene may be propylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-octene, etc., preferably propylene, 1-butene, 1-hexene, and 4-methyl-1-pentene.
[0108] (Polyethylene wax used as raw material)
[0109] The unmodified polyolefin wax may be a polyethylene wax which is a homopolymer of ethylene or a copolymer of ethylene and an α-olefin having 3 to 12 carbon atoms.
[0110] Examples of the polyethylene wax which is a homopolymer of ethylene include high-density polyethylene wax, medium-density polyethylene wax, low-density polyethylene wax, and linear low-density polyethylene wax.
[0111] In the polyethylene wax which is a copolymer of ethylene and an α-olefin having 3 or more carbon atoms and 12 or less, the ratio of the structural unit derived from ethylene is preferably 91.0 mol% to 99.9 mol%, more preferably 93.0 mol% to 99.9 mol%, further preferably 95.0 mol% to 99.9 mol%, and particularly preferably 95.0 mol% to 99.0 mol%. On the other hand, the ratio of the structural unit derived from the α-olefin having 3 or more carbon atoms is preferably 0.1 mol% to 9.0 mol%, more preferably 0.1 mol% to 7.0 mol%, further preferably 0.1 mol% to 5.0 mol%, and particularly preferably 1.0 mol% to 5.0 mol% (the total amount of the structural unit derived from ethylene and the structural unit derived from the α-olefin having 3 or more carbon atoms is 100 mol%).
[0112] The example of the alpha-olefin of the above-mentioned carbon number of 3 or more and 12 or less includes propylene, 1-butene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, 3-methyl-1-pentene, 1-octene, 1-decene, and 1-dodecene and other linear or branched alpha-olefins. Among them, preferably propylene, 1-butene, 1-hexene, 4-methyl-1-pentene, and 1-octene, more preferably alpha-olefins with carbon number of 3 or more and 8 or less, further preferably propylene and 1-butene, particularly preferably 1-butene. If ethylene is copolymerized with propylene and 1-butene, then even if propylene and 1-butene are added in small amounts, the melting point is effectively reduced, and the crystallinity of polyolefin wax is increased, therefore, compatibilizer (C) hardens and is not easy to be sticky. Therefore, if such a compatibilizer (C) is used, it is not easy to produce stickiness on the surface of the molded body. In addition, the structural unit derived from these α-olefins may contain only one kind or two or more kinds.
[0113] In particular, when the thermoplastic resin (A) is polyethylene, by using a modified polyethylene wax as the compatibilizer (C), the compatibility between the thermoplastic resin (A) and the compatibilizer (C) can be improved, thereby improving the processability, heat resistance, mechanical strength, and appearance of the molded body.
[0114] (Polypropylene wax as raw material)
[0115] The unmodified polyolefin wax may be a polypropylene wax which is a homopolymer of propylene or a copolymer of propylene and ethylene or an α-olefin having 4 to 12 carbon atoms.
[0116] These polypropylene waxes may be obtained by homopolymerizing propylene or copolymerizing propylene with other α-olefins in the presence of a stereospecific catalyst, or may be obtained by thermally decomposing high molecular weight polypropylene. Alternatively, the polypropylene wax may be obtained by solvent fractionation using the difference in solubility of polypropylene in a solvent, or by molecular distillation and fractionation using the difference in boiling points.
[0117] When the polypropylene wax is a copolymer of propylene and ethylene, the ratio of the structural unit derived from propylene can be set to 60 mol% to 99.5 mol%, preferably 80 mol% to 99 mol%, more preferably 90 mol% to 98.5 mol%, and particularly preferably 95 mol% to 98 mol% (the total amount of the structural unit derived from propylene and the structural unit derived from ethylene is set to 100 mol%). If a propylene-based polymer having a high ratio of structural units derived from propylene is used, the moldability, appearance, and heat resistance of the molded article become good.
[0118] In the case where the polypropylene wax is a copolymer of propylene and an α-olefin having 4 to 12 carbon atoms, examples of the α-olefin having 4 to 12 carbon atoms include linear or branched α-olefins such as 1-butene, 1-pentene, 3-methyl-1-butene, 1-hexene, 4-methyl-1-pentene, 3-methyl-1-pentene, 1-octene, 1-decene, and 1-dodecene. Among them, 1-butene is preferred. The structural unit derived from the α-olefin may include only one kind or two or more kinds.
[0119] When the propylene polymer is a copolymer of propylene and an α-olefin having 4 to 12 carbon atoms, the ratio of the structural unit derived from propylene is preferably 60 mol% to 90 mol%, more preferably 65 mol% to 88 mol%, further preferably 70 mol% to 85 mol%, particularly preferably 75 mol% to 82 mol%. On the other hand, the ratio of the structural unit derived from the α-olefin having 4 to 12 carbon atoms is preferably 10 mol% to 40 mol%, more preferably 12 mol% to 35 mol%, further preferably 15 mol% to 30 mol%, particularly preferably 18 mol% to 25 mol% (the total amount of the structural unit derived from propylene and the structural unit derived from the α-olefin having 4 to 12 carbon atoms is 100 mol%).
[0120] If the composition of the propylene α-olefin copolymer is within the above range, the appearance, mechanical strength and heat resistance of the molded body will be improved. In particular, it is possible that the time for the resin composition to flow in the mold is longer due to the slow crystallization rate, so the appearance of the molded body is improved. In addition, if the composition of the propylene α-olefin copolymer is within the above range, the heat resistance and mechanical strength of the injection body are also improved.
[0121] In particular, when the thermoplastic resin (A) is polypropylene, by using a modified product of polypropylene wax as the compatibilizer (C), the compatibility between the thermoplastic resin (A) and the compatibilizer (C) can be improved, thereby improving the processability, heat resistance, mechanical strength, and appearance of the molded body.
[0122] (Poly 4-methyl-1-pentene wax used as raw material)
[0123] The unmodified polyolefin wax may be poly-4-methyl-1-pentene wax which is a homopolymer of 4-methyl-1-pentene or a copolymer of 4-methyl-1-pentene and other α-olefins.
[0124] The poly 4-methyl-1-pentene wax may be a poly 4-methyl-1-pentene wax obtained by thermally decomposing a 4-methyl-1-pentene polymer described in International Publication No. 2011 / 055803, a 4-methyl-1-pentene polymer (B-1) and a 4-methyl-1-pentene polymer (B-2) described in Japanese Patent Application Publication No. 2005-028187, or the like.
[0125] (Method for producing polyolefin wax as raw material)
[0126] These unmodified polyolefin waxes can be synthesized by polymerization of raw materials or by thermal decomposition of high molecular weight (co)polymers. The thermal decomposition can be carried out at 300 to 450°C for 5 minutes to 10 hours. In the unmodified polyolefin wax produced by thermal decomposition under the above conditions, unsaturated terminals are present. 1 If the number of vinylidene groups per 1000 carbon atoms measured by H-NMR is 0.5 or more and 5 or less, the compatibilizer (C) is easily compatible with the natural fiber (B), and is therefore preferred. Alternatively, these unmodified polyolefin waxes may be polyolefin waxes obtained by solvent fractionation of a high molecular weight (co)polymer using a difference in solubility in a solvent, or polyolefin waxes obtained by molecular distillation and fractionation using a difference in boiling points.
[0127] The synthesis of the unmodified polyolefin wax obtained by polymerization of the raw materials can be carried out by a known method such as a method of polymerization using a Ziegler-Natta catalyst or a metallocene catalyst.
[0128] For example, a suspension polymerization method in which the monomers and polymers used as raw materials are suspended in an inactive hydrocarbon medium such as hexane in the form of particles and polymerized, a gas phase polymerization method in which polymerization is performed without using a solvent, and a solution polymerization method in which polymerization is performed in a melted state in an inactive hydrocarbon medium, etc. can be adopted. Among them, the solution polymerization method is preferably used from the perspective of being cheap and having good quality. The polymerization can be performed by an intermittent method or a continuous method. In addition, the polymerization can also be performed in two or more steps with different reaction conditions.
[0129] Examples of inactive hydrocarbon media used in suspension polymerization and solution polymerization include aliphatic hydrocarbons such as propane, butane, pentane, hexane, heptane, octane, decane, dodecane and kerosene, alicyclic hydrocarbons such as cyclopentane, cyclohexane and methylcyclopentane, aromatic hydrocarbons such as benzene, toluene and xylene, halogenated hydrocarbons such as vinyl chloride, chlorobenzene and methylene chloride, etc. These inactive hydrocarbon media can be used alone or in combination of two or more. In addition, the so-called bulk polymerization method using α-olefin itself as a solvent can also be adopted.
[0130] As the above-mentioned catalyst, a metallocene catalyst is preferred. Examples of the metallocene catalyst include the following catalysts, wherein the catalyst comprises:
[0131] (a) a metallocene compound of a transition metal selected from Group 4 of the Periodic Table of Elements, and
[0132] (b) (b-1) an organoaluminum oxy-compound, (b-2) a compound that reacts with the metallocene compound (a) to form an ion pair (hereinafter also referred to as "ionized ionic compound"), or (b-3) an organoaluminum compound (see Japanese Patent Application Laid-Open No. 08-239414 and International Publication No. 2007 / 114102).
[0133] (a) Metallocene compounds of transition metals selected from Group 4 of the periodic table Examples of (a) include metallocene compounds described in Japanese Patent Application Laid-Open No. 08-239414 and International Publication No. 2007 / 114102. Among them, bis(n-butylcyclopentadienyl)zirconium dichloride and bis(n-butylcyclopentadienyl)zirconium dimethyl are preferred.
[0134] As the (b-1) organoaluminum oxy-compound, known aluminoxanes such as those described in Japanese Unexamined Patent Publication No. 08-239414 and International Publication No. 2007 / 114102 can be used. Among them, methylaluminoxane and modified methylaluminoxane (MMAO) prepared using trimethylaluminum and triisobutylaluminum are preferred because they are commercially available and easily available.
[0135] Examples of (b-2) ionizing ionic compounds include ionizing ionic compounds described in Japanese Patent Application Laid-Open No. 08-239414 and International Publication No. 2007 / 114102. Among them, triphenylcarbonium tetrakis(pentafluorophenyl)borate and N,N-dimethylanilinium tetrakis(pentafluorophenyl)borate are preferred because they are commercially available and can easily improve polymerization activity.
[0136] Examples of (b-3) organoaluminum compounds include those described in International Publication No. 2007 / 114102. Among them, trimethylaluminum, triethylaluminum, and triisobutylaluminum are preferred because they are commercially available and easily available, and triisobutylaluminum is more preferred because it is easy to handle.
[0137] When the compounds (b-1) to (b-3) are combined, a combination of triisobutylaluminum and triphenylcarbonium tetrakis(pentafluorophenyl)borate and a combination of triisobutylaluminum and N,N-dimethylanilinium tetrakis(pentafluorophenyl)borate are preferred because they can greatly improve the polymerization activity.
[0138] When the monomers are polymerized using the above-mentioned metallocene-based catalyst, the content of each component may be set as follows.
[0139] (1) (a) The metallocene compound is 10 -9 More than 10 moles -1 mol or less, preferably 10 -8 More than 10 moles -2 Below mole
[0140] (2) (b-1) The organoaluminum oxy-compound is an amount in which the molar ratio [Al / M] of the aluminum atom (Al) in the compound (b-1) to the total transition metal atoms (M) in the metallocene compound (a) is 0.01 to 5000, preferably 0.05 to 2000.
[0141] (3) The ionic compound (b-2) is an amount in which the molar ratio of the compound (b-2) to the total transition metal atoms (M) in the metallocene compound (a) [(b-2) / M] is 1 to 10, preferably 1 to 5.
[0142] (4) The organoaluminum compound (b-3) is an amount in which the molar ratio of the compound (b-3) to the total transition metal atoms (M) in the metallocene compound (a) [(b-3) / M] is 0.01 to 50,000, preferably 0.05 to 10,000.
[0143] The polymerization temperature at this time may be set to 10° C. to 200° C., preferably 60° C. to 180° C., more preferably 75° C. to 170° C. The polymerization pressure may be set to 7.8 MPa-G (G is a gauge pressure) or higher than normal pressure, preferably 4.9 MPa-G or higher than normal pressure.
[0144] During polymerization, the monomers (ethylene, α-olefin) used as raw materials may be supplied to the polymerization system in such a ratio as to obtain the unmodified polyolefin wax having the above composition. In addition, a molecular weight modifier such as hydrogen may be added during polymerization.
[0145] The polymerization liquid obtained by polymerizing the raw materials in this way can be treated by a conventional method to obtain an unmodified polyolefin wax.
[0146] In addition, the polymer obtained by the above method can be further purified. The purification can be carried out by a method of degassing under vacuum at a temperature above the melting point, a method of removing low molecular weight parts by dissolving it in a solvent such as toluene, xylene, hexane, and heptane, adding a polar solvent such as methanol and acetone, and filtering it, and a method of removing high molecular weight parts or low molecular weight parts by dissolving the entire amount in a solvent and precipitating it at a specific temperature.
[0147] The number average molecular weight (Mn) and intrinsic viscosity [η] of the unmodified polyolefin wax tend to decrease if the polymerization temperature during polymerization is increased or the hydrogen concentration is increased, and can be controlled within the above range. Alternatively, it can be adjusted by the amount of the organoaluminum oxide compound or ionized ionic compound used as a co-catalyst. In addition, it can also be adjusted by purification after polymerization.
[0148] The content of the structural unit derived from ethylene and each α-olefin can be controlled by adjusting the amount added during polymerization, as well as by adjusting the type of catalyst, polymerization temperature, and the like.
[0149] The Mw / Mn of unmodified polyolefin wax can be controlled by catalyst type, polymerization temperature, etc. Ziegler-Natta catalysts and metallocene catalysts are usually used in polymerization, but in order to achieve the Mw / Mn of the preferred range, metallocene catalysts are preferably used. In addition, the preferred range can also be achieved by purifying using solvent fractionation (which utilizes the difference in solubility in the solvent to fractionate) or distillation.
[0150] The softening point of unmodified polyolefin wax can be adjusted by the composition of ethylene and α-olefin. For example, if it is a copolymer of ethylene and α-olefin, the softening point can be reduced by increasing the content of α-olefin. In addition, it can also be controlled by catalyst type, polymerization temperature, etc. In addition, it can also be adjusted by purification after polymerization.
[0151] The density of the unmodified polyolefin wax can be adjusted by the composition of ethylene and α-olefin and the polymerization temperature or hydrogen concentration during polymerization.
[0152] (Modified polyolefin wax as a grafted modified product of unmodified polyolefin wax)
[0153] The grafted modified product of unmodified polyolefin wax can be obtained by grafting the unmodified polyolefin wax with an unsaturated carboxylic acid, grafting the unmodified polyolefin wax with a styrene, grafting the unmodified polyolefin wax with a sulfonate, or grafting the unmodified polyolefin wax with a mixture thereof. These grafting modifications can be carried out by known methods. For example, the grafted modified product of unmodified polyolefin wax can be obtained by a method of melt-kneading unmodified polyolefin wax and unsaturated carboxylic acid, styrene or sulfonate in the presence of a polymerization initiator such as an organic peroxide, or by a method of kneading a solution obtained by dissolving unmodified polyolefin wax, which will become a raw material, and unsaturated carboxylic acid, styrene or sulfonate in an organic solvent in the presence of a polymerization initiator such as an organic peroxide.
[0154] Melt kneading can be carried out using an autoclave, a Henschel mixer, a V-type mixer, a tumbler mixer, a ribbon mixer, a single screw extruder, a multi-screw extruder, a kneader, and a Banbury mixer, etc. Among them, from the viewpoint of making each component more uniformly dispersed and reacting efficiently, it is preferred to use an apparatus such as an autoclave that can easily adjust the residence time and can take a longer residence time for intermittent melt kneading.
[0155] Examples of unsaturated carboxylic acids used for graft modification include: acrylic acid esters including methyl acrylate, ethyl acrylate, butyl acrylate, sec-butyl acrylate, isobutyl acrylate, propyl acrylate, isopropyl acrylate, 2-octyl acrylate, dodecyl acrylate, stearyl acrylate, hexyl acrylate, isohexyl acrylate, phenyl acrylate, 2-chlorophenyl acrylate, diethylaminoethyl acrylate, 3-methoxybutyl acrylate, diethylene glycol ethoxylate, and 2,2,2-trifluoroethyl acrylate; acrylic acid esters including methyl methacrylate, ethyl methacrylate, butyl methacrylate, sec-butyl methacrylate, isobutyl methacrylate, propyl methacrylate, isopropyl methacrylate, 2-octyl methacrylate, dodecyl methacrylate, stearyl methacrylate, hexyl acrylate, isohexyl acrylate, phenyl acrylate, 2-chlorophenyl acrylate, diethylaminoethyl acrylate, 3-methoxybutyl acrylate, diethylene glycol ethoxylate, and 2,2,2-trifluoroethyl acrylate; acrylic acid esters including methyl methacrylate, ethyl methacrylate, butyl methacrylate, sec-butyl methacrylate, isobutyl methacrylate, propyl methacrylate, isopropyl methacrylate, 2-octyl methacrylate, dodecyl methacrylate, stearyl methacrylate The invention also includes methacrylates such as stearyl methacrylate, hexyl methacrylate, decyl methacrylate, phenyl methacrylate, 2-chlorohexyl methacrylate, diethylaminoethyl methacrylate, 2-hexylethyl methacrylate, and 2,2,2-trifluoroethyl methacrylate; maleic acid esters such as ethyl maleate, propyl maleate, butyl maleate, diethyl maleate, dipropyl maleate, and dibutyl maleate; fumaric acid esters such as ethyl fumarate, butyl fumarate, and dibutyl fumarate; unsaturated dicarboxylic acids such as maleic acid, fumaric acid, itaconic acid, crotonic acid, nadic acid, and methylhexahydrophthalic acid; anhydrides of unsaturated carboxylic acids such as maleic anhydride, itaconic anhydride, citraconic anhydride, allyl succinic anhydride, glutaconic anhydride, and nadic anhydride, etc. Among them, maleic anhydride is preferred due to its high reactivity with unmodified polyolefin wax, small structural changes due to polymerization, and a tendency to be stable as a basic structure. In addition, due to the above-mentioned characteristics of maleic anhydride, the modified polyolefin wax obtained by maleic anhydride modification also maintains a stable state under a high temperature environment during molding, and the degree of interaction with the surface of the natural fiber (B) is not easy to reduce. As a result, it is believed that a molded body with excellent appearance, heat resistance, processability, and mechanical strength can be obtained.
[0156] The acid value (JIS K 2501 (2003)) of the modified polyolefin wax graft-modified with an unsaturated carboxylic acid is preferably from 1 mgKOH / g to 100 mgKOH / g, more preferably from 20 mgKOH / g to 90 mgKOH / g, and still more preferably from 30 mgKOH / g to 87 mgKOH / g.
[0157] If the acid value of the modified polyolefin wax obtained by grafting modification with an unsaturated carboxylic acid is within the above range, the appearance, processability, heat resistance, and mechanical strength of the molded body are improved. It is believed that the reason is that the affinity of the compatibilizer (C) and the natural fiber (B) is fully improved, and on the other hand, the fusion of the compatibilizer (C) and the thermoplastic resin (A) can be fully maintained, so the compatibility of the thermoplastic resin (A) and the natural fiber (B) is fully improved, thereby improving the uniformity of the entire system and improving the dispersibility of the natural fiber (B). In particular, even if the modified polyolefin wax obtained by grafting modification with an unsaturated carboxylic acid is a low molecular weight, the above effect can be fully achieved.
[0158] In particular, when the processability and appearance of the molded article are important, the acid value of the modified polyolefin wax obtained by graft modification with an unsaturated carboxylic acid is preferably 1 mgKOH / g or more and 55 mgKOH / g or less. The acid value is more preferably 20 mgKOH / g or more, further preferably 30 mgKOH / g or more, and particularly preferably 42 mgKOH / g or more. In addition, the acid value is more preferably 50 mgKOH / g or less, further preferably 48 mgKOH / g or less, and particularly preferably 46 mgKOH / g or less.
[0159] On the other hand, when emphasis is placed on the heat resistance and mechanical strength of the molded article, the acid value of the modified polyolefin wax obtained by graft modification with an unsaturated carboxylic acid is preferably from 40 mgKOH / g to 100 mgKOH / g, more preferably from 50 mgKOH / g to 100 mgKOH / g, further preferably from 60 mgKOH / g to 100 mgKOH / g, further preferably from 60 mgKOH / g to 95 mgKOH / g, further preferably from 60 mgKOH / g to 90 mgKOH / g, and particularly preferably from 80 mgKOH / g to 90 mgKOH / g.
[0160] Examples of styrenes used for graft modification include styrene, α-methylstyrene, o-methylstyrene, p-methylstyrene, m-methylstyrene, p-chlorostyrene, m-chlorostyrene, p-chloromethylstyrene and the like.
[0161] The content of styrenes in the modified polyolefin wax obtained by graft modification with styrenes is preferably 1 to 500 parts by mass, more preferably 5 to 200 parts by mass, further preferably 20 to 160 parts by mass, and particularly preferably 22 to 30 parts by mass. If the content of styrenes is within the above range, the compatibility of the modified polyolefin wax and the natural fiber (B) becomes good, and excessive interaction that causes viscosity increase can be suppressed, thereby improving the processability, appearance, heat resistance, and mechanical strength of the molded body.
[0162] When the graft modified product of unmodified polyolefin wax is graft modified with both unsaturated carboxylic acid and styrene, the graft amount ratio of unsaturated carboxylic acid to styrene "(unsaturated carboxylic acid) / (styrene)" is preferably 0.01 to 1, more preferably 0.03 to 0.8, and further preferably 0.05 to 0.6. By making their graft amount ratio greater than 0.01, the unsaturated carboxylic acid can fully interact with the surface of the natural fiber (B), thereby fully improving the impact resistance of the molded body. By making their graft amount ratio less than 1, the melt viscosity of the graft modified product of unmodified polyolefin wax can be appropriately suppressed, thereby facilitating the production.
[0163] The content of styrene in the modified polyolefin wax obtained by graft modification with sulfonate styrene is preferably 0.1 mmol to 100 mmol, more preferably 5 mmol to 50 mmol per 1 g of the modified polyolefin wax. If the modification amount based on sulfonate is within the above range, the dispersibility of the natural fiber (B) becomes better, and the mechanical strength of the molded body is easily improved.
[0164] The graft-modified modified polyolefin wax may be a commercial product, and examples of the commercial products include Diacarna PA30 ("Diacarna" is a registered trademark of Mitsubishi Chemical Corporation), High Wax Acid-treated 2203A manufactured by Mitsui Chemicals, Inc., and oxidized paraffin wax manufactured by Nippon Seiro Co., Ltd.
[0165] (Modified polyolefin wax as an air oxidant of unmodified polyolefin wax)
[0166] The air oxidation of unmodified polyolefin wax can be obtained by stirring the unmodified polyolefin wax as a raw material in a molten state and contacting it with oxygen or an oxygen-containing gas. The unmodified polyolefin wax as a raw material can be molten at a temperature of 130° C. to 200° C., preferably 140° C. to 170° C.
[0167] The oxygen or oxygen-containing gas may be pure oxygen (oxygen obtained by conventional liquid air fractionation or water electrolysis, and may contain other components to a certain extent as impurities), or a mixed gas of pure oxygen and other gases (such as air, ozone, etc.).
[0168] The contact between the unmodified polyolefin wax and oxygen or oxygen-containing gas is preferably carried out by the following method: oxygen-containing gas is continuously supplied from the lower part of the reactor containing the molten unmodified polyolefin wax to contact the unmodified polyolefin wax. In this case, the oxygen-containing gas is preferably supplied in a manner that 1.0 NL or more and 8.0 NL or less of oxygen is supplied per minute relative to 1 kg of the unmodified polyolefin wax.
[0169] The air oxidation acid value (JIS K 5902 (2006)) of the polyolefin wax thus obtained is preferably from 1 mgKOH / g to 100 mgKOH / g, more preferably from 20 mgKOH / g to 90 mgKOH / g, and further preferably from 30 mgKOH / g to 87 mgKOH / g.
[0170] If the acid value of the air oxide of the polyolefin wax is within the above range, the appearance, processability, heat resistance, and mechanical strength of the molded body are improved. It is believed that the reason is that the affinity of the compatibilizer (C) and the natural fiber (B) is fully improved, and on the other hand, the fusion of the compatibilizer (C) and the thermoplastic resin (A) can be fully maintained, so the compatibility of the thermoplastic resin (A) and the natural fiber (B) is fully improved, thereby improving the uniformity of the entire system, and the dispersibility of the natural fiber (B) becomes good. In particular, even if the air oxide of the polyolefin wax is a low molecular weight, the above effect can be fully achieved.
[0171] In particular, when the processability and appearance of the molded article are important, the acid value of the air oxide of the polyolefin wax is preferably 1 mgKOH / g or more and 55 mgKOH / g or less. The acid value is more preferably 20 mgKOH / g or more, further preferably 30 mgKOH / g or more, and particularly preferably 42 mgKOH / g or more. In addition, the acid value is more preferably 50 mgKOH / g or less, further preferably 48 mgKOH / g or less, and particularly preferably 46 mgKOH / g or less.
[0172] On the other hand, when emphasis is placed on the heat resistance and mechanical strength of the molded article, the acid value of the air oxide of the polyolefin wax is preferably from 40 mgKOH / g to 100 mgKOH / g, more preferably from 50 mgKOH / g to 100 mgKOH / g, further preferably from 60 mgKOH / g to 100 mgKOH / g, further preferably from 60 mgKOH / g to 95 mgKOH / g, further preferably from 60 mgKOH / g to 90 mgKOH / g, particularly preferably from 80 mgKOH / g to 90 mgKOH / g.
[0173] (Physical properties of modified polyolefin wax)
[0174] The modified polyolefin wax preferably satisfies any one or more of the following requirements (i) to (iv), and more preferably satisfies all of the requirements.
[0175] (i) the number average molecular weight (Mn) converted by polystyrene measured by gel permeation chromatography (GPC) is more than 300 and 20000. The above-mentioned number average molecular weight (Mn) is preferably more than 500 and less than 18000, more preferably more than 1000 and less than 12000, more preferably more than 1500 and less than 12000, more preferably more than 3700 and less than 12000, more preferably more than 6000 and less than 12000, and particularly preferably more than 8000 and less than 10000. If the number average molecular weight (Mn) is within the above range, the dispersibility of the natural fiber (B) in the resin combination can be improved more well, and the appearance, heat resistance and mechanical strength of the molded body can be further improved. In addition, the processability and mixing property of the resin combination also become better.
[0176] (ii) The softening point measured in accordance with JIS K 2207 (2006) is 70°C to 170°C. The softening point is preferably 160°C to 160°C, more preferably 150°C to 145°C, and even more preferably 80°C to 80°C, more preferably 90°C to 95°C, and even more preferably 105°C. When the softening point is within the above range, the appearance, processability, heat resistance, and mechanical strength of the molded article are further improved.
[0177] (iii) The density measured by the density gradient tube method is 830 kg / m 3 Above 1200kg / m 3 The above density is preferably 860 kg / m 3 Above 1100kg / m 3 Below, more preferably 890kg / m 3 Above 1000kg / m 3Below, more preferably 895kg / m 3 Above 960kg / m 3 Below, particularly preferably 895 kg / m 3 Above 935kg / m 3 If the density is within the above range, the dispersibility of the natural fiber (B) in the resin composition can be improved, and the appearance, heat resistance, and mechanical strength of the molded body can be further improved. In addition, the processability and mixing properties of the resin composition are also improved. Although the reason is unclear, the density of the natural fiber (B) is usually 1000kg / m 3 In contrast, it is believed that the reason is that by using a compatibilizer (C) having a lower density than the above, when the compatibilizer (C) is localized on the surface of the natural fiber (B), the surface tension of the natural fiber (B) is reduced, thereby reducing the cohesive force of the natural fiber (B).
[0178] It should be noted that the difference between the density of the thermoplastic resin (A) and the density of the compatibilizer (C) is preferably less than 50 kg / m 3 , more preferably less than 30kg / m 3 , further preferably less than 15kg / m 3 . If the density difference is within the above range, the appearance, processability, heat resistance, and mechanical strength of the molded body are further improved. Although the reason is unclear, it is believed that materials with similar densities tend to be easily mixed with each other. That is, it is believed that the reason is that the compatibility between the thermoplastic resin (A) and the compatibilizer (C) is increased, thereby improving the dispersibility of the natural fiber (B) coated with the compatibilizer (C) in the thermoplastic resin (A). In addition, it is believed that if the density difference is within the above range, the exudation of the compatibilizer (C) from the thermoplastic resin (A) can be suppressed, and therefore, the appearance, heat resistance, and mechanical strength of the molded body are further improved.
[0179] (iv) The ratio of the weight average molecular weight to the number average molecular weight (Mw / Mn) measured by gel permeation chromatography (GPC) is 7.0 or less. Mw / Mn is preferably 5.0 or less, and more preferably 3.0 or less. If Mw / Mn is within the above range, there are fewer low molecular weight components that cause the physical properties to decrease, and therefore, the appearance, heat resistance, and mechanical strength of the molded body are further improved.
[0180] When two or more modified polyolefin waxes are used in combination as the compatibilizer (C), if the modified polyolefin waxes used in combination have different melting points and softening points, the processability of the resin composition and the mechanical strength of the molded product are easily improved.
[0181] When two or more modified polyolefin waxes are used in combination, the difference between the softening point of the modified polyolefin wax (CWH) having the highest softening point and the softening point of the modified polyolefin wax (CWL) having the lowest softening point is preferably 5°C or more, more preferably 10°C or more, further preferably 20°C or more, further preferably 30°C or more, particularly preferably 40°C or more.
[0182] If the difference between the softening point of the modified polyolefin wax (CWH) and the softening point of the modified polyolefin wax (CWL) is within the above range, the processability and mechanical strength of the molded body are improved. In addition, the reduction of torque and the suppression of shear heat generation when using an extruder can be achieved. Although the reason is unclear, it is believed that the modified polyethylene wax (CWL) with a lower softening point melts at an earlier time in the system, thereby improving the dispersibility of the natural fiber (B) in the thermoplastic resin (A), or effectively reducing the torque of the extruder. In addition, it is believed that the melted modified polyethylene wax (CWL) suppresses the shear heat generation in the system, thereby suppressing the burning of the natural fiber (B). On the other hand, after the dispersibility of the natural fiber (B) is improved, the modified polyolefin wax (CWH) with a higher softening point melts, thereby improving the contact efficiency of the modified polyolefin wax (CWH) and the natural fiber (B), and the modification effect of the natural fiber (B) brought by the modified polyolefin wax (CWH) becomes higher. It is considered that these actions can improve the processability of the resin composition and also effectively improve the mechanical properties.
[0183] The softening point of the modified polyolefin wax (CWH) having the highest softening point is preferably 100°C to 180°C, more preferably 110°C to 175°C. The softening point of the modified polyolefin wax (CWL) having the lowest softening point is preferably 80°C to 150°C, more preferably 90°C to 145°C.
[0184] The melting point of the modified polyolefin wax (CWH) having the highest softening point is preferably 90°C to 170°C, more preferably 100°C to 165°C. The melting point of the modified polyolefin wax (CWL) having the lowest softening point is preferably 70°C to 140°C, more preferably 80°C to 135°C.
[0185] At this time, the more the amount of modified polyolefin wax (CWL) having the lowest softening point is added, the easier it is to improve the dispersibility of the natural fiber (B). Specifically, the mass ratio (CWH) / (CWL) of the modified polyolefin wax (CWH) to the modified polyolefin wax (CWL) is preferably 1 / 200 to 1 / 1, more preferably 1 / 50 to 1 / 1.1, further preferably 1 / 20 to 1 / 1.3, and particularly preferably 1 / 10 to 1 / 1.5.
[0186] The modified polyolefin wax (CWH) having the highest softening point is preferably a modified polyolefin wax graft-modified with an unsaturated carboxylic acid.
[0187] In addition, the acid value of the modified polyolefin wax (CWH) having the highest softening point is preferably 40 mgKOH / g to 100 mgKOH / g, more preferably 50 mgKOH / g to 100 mgKOH / g, further preferably 60 mgKOH / g to 100 mgKOH / g, further preferably 60 mgKOH / g to 95 mgKOH / g, further preferably 60 mgKOH / g to 90 mgKOH / g, and particularly preferably 80 mgKOH / g to 90 mgKOH / g. When the acid value of the modified polyolefin wax (CWH) having the highest softening point is within the above range, the heat resistance and mechanical strength of the molded article are further improved.
[0188] The acid value of the modified polyolefin wax (CWL) with the lowest softening point is preferably less than 90 mgKOH / g, more preferably less than 65 mgKOH / g. The lower limit of the acid value of the modified polyolefin wax (CWL) with the lowest softening point is not particularly limited, but is preferably more than 15 mgKOH / g. If the acid value of the modified polyolefin wax (CWL) with the lowest softening point is within the above range, the heat resistance of the molded body can be improved (specifically, the load deflection temperature, softening point, etc.) without reducing the processability of the resin composition. Although the reason is unclear, it is believed that the reason is that even if the molded body is heated to a temperature above the softening point, the modified polyolefin wax (CWL) is not easy to detach from the surface of the natural fiber (B), so even if heated, it is not easy to improve the molecular mobility of the natural fiber (B).
[0189] (2) Petroleum resin (C2)
[0190] Petroleum resin (C2) can be an aliphatic petroleum resin with C5 fraction of tar naphtha as the main raw material, an aromatic petroleum resin with C9 fraction as the main raw material, and their copolymerized petroleum resins, etc. That is, examples of petroleum resin (C2) include C5-based petroleum resin (resin obtained by polymerizing C5 fraction of naphtha decomposition oil), C9-based petroleum resin (resin obtained by polymerizing C9 fraction of naphtha decomposition oil), and C5C9 copolymerized petroleum resin (resin obtained by copolymerizing C5 fraction and C9 fraction of naphtha decomposition oil), etc. If compatibilizer (C) is petroleum resin (C2), the mixing property of compatibilizer (C) and other components becomes good.
[0191] In addition, as petroleum resin (C2), benzofuran indene resins such as styrenes, indenes, benzofurans, other dicyclopentadienes, etc. containing tar fractions, alkylphenol resins represented by condensates of p-tert-butylphenol and acetylene, and xylene resins formed by reacting o-xylene, p-xylene or m-xylene with formalin, etc. can be used. It should be noted that petroleum resin (C2) can also be produced using raw materials from biomass.
[0192] (3) Other compatibilizers (C3)
[0193] Moreover, as a compatibilizer (C), a rosin-based resin and a terpene-based resin can also be used.
[0194] Examples of the rosin-based resin include natural rosin, polymerized rosin, and rosin derivatives such as phenol-modified products and esters and hydrogenated products thereof. It should be noted that the other compatibilizer (C3) can also be produced using raw materials derived from biomass.
[0195] 1-4. Processing aids (D)
[0196] The processing aid (D) improves the crystallinity of the thermoplastic resin (A) to improve the processability of the resin composition.
[0197] As the processing aid (D), a polyolefin wax which is a synthetic material of the compatibilizer (C) can be used. For example, when the thermoplastic resin (A) is a polyolefin (A-1), it is preferably a resin of a type different from that of the polyolefin (A-1) (when the polyolefin (A-1) is polyethylene, the processing aid (D) is polypropylene wax, and when the polyolefin (A-1) is polypropylene, the processing aid (D) is polyethylene wax, etc.). For example, the processing aid (D) is preferably polyethylene wax. It should be noted that the processing aid (D) can also be produced using raw materials from biomass.
[0198] 1-5. Other ingredients
[0199] The resin composition and the molded body may contain conventionally known additives, such as antioxidants, weathering stabilizers, ultraviolet absorbers, antistatic agents, antiskid agents, anti-caking agents, antifogging agents, crystal nucleating agents, lubricants, pigments, dyes, anti-aging agents, hydrochloric acid absorbers, inorganic or organic fillers, organic or inorganic foaming agents, crosslinking agents, crosslinking aids, adhesives, softeners, flame retardants, etc., as required. The content of the above-mentioned various additives is preferably 5% by mass or less, more preferably 3% by mass or less, relative to the total mass of the resin composition.
[0200] 1-6. Composition ratio
[0201] From the viewpoint of improving the mechanical strength and heat resistance of the molded body, the resin composition and the molded body preferably contain more thermoplastic resin (A). On the other hand, from the viewpoint of improving the impact resistance, flexibility, grip and impact absorption of the molded body, it is preferred to make the amount of components (especially natural fiber (B)) other than the thermoplastic resin (A) more. From the viewpoint of obtaining their balance, in the resin composition and the molded body, the ratio ((A) / (W)) of the total mass of the thermoplastic resin (A) relative to the total mass (W) of the resin composition is preferably 0.01 or more, more preferably 0.1 or more, further preferably 0.3 or more, and particularly preferably 0.35 or more. In addition, it is preferably 0.99 or less, more preferably 0.9 or less, further preferably 0.7 or less, and particularly preferably 0.5 or less. That is, it is preferably 0.01 or more and 0.99 or less, more preferably 0.1 or more and 0.9 or less, further preferably 0.3 or more and 0.7 or less, and particularly preferably 0.35 or more and 0.5 or less.
[0202] In addition, in the resin composition and the molded product, the ratio of the total mass of the natural fiber (B) to the total mass of the thermoplastic resin (A) ((B) / (A)) is preferably from 0.01 to 10.00, more preferably from 0.10 to 5.00, further preferably from 0.25 to 2.00, further preferably from 0.30 to 1.50, and particularly preferably from 0.50 to 1.40.
[0203] When resin composition and molded body include compatibilizer (C), the amount of compatibilizer (C) is more, then the processability of resin composition, the appearance of molded body, heat resistance, impact resistance and wear resistance are improved. On the other hand, by suppressing the amount of compatibilizer (C) in a suitable range, it is possible to adjust compatibility and heat resistance stability to a suitable range, in addition, it is not easy to produce smoke, odor, etc. during molding, and then it is also possible to suppress the generation of residues (resin, low molecular weight components and additives attached to the burnt accumulation near the outlet of the molding machine), burnt, etc. From the viewpoint of obtaining their equilibrium, in resin composition and molded body, the ratio ((C) / (A)) of the gross mass of compatibilizer (C) relative to the gross mass of thermoplastic resin (A) is preferably 0.005 or more than 1, more preferably 0.008 or more than 0.8, more preferably 0.01 or more than 0.6, more preferably 0.012 or more than 0.5, particularly preferably 0.015 or more than 0.4.
[0204] In addition, from the same point of view, in the resin composition and the molded body, the ratio of the total mass of the compatibilizer (C) to the total mass of the natural fiber (B) ((C) / (B)) is preferably from 0.002 to 1, more preferably from 0.003 to 0.8, further preferably from 0.004 to 0.6, further preferably from 0.006 to 0.4, and particularly preferably from 0.008 to 0.3.
[0205] In addition, from the same point of view, in the resin composition and the molded product, the ratio of the total mass of the compatibilizer (C) to the total mass of the thermoplastic resin (A), the natural fiber (B) and the compatibilizer (C) ((C) / ((A) + (B) + (C))) is preferably from 0.002 to 0.8, more preferably from 0.005 to 0.7, further preferably from 0.008 to 0.1, further preferably from 0.012 to 0.09, and particularly preferably from 0.015 to 0.08.
[0206] From the viewpoint of improving the mechanical strength and heat resistance of the molded body, resin composition and molded body preferably include more thermoplastic resin (A). On the other hand, from the viewpoint of improving the impact resistance, flexibility, grip and impact absorption of the molded body, it is preferred to make the amount of the components other than the thermoplastic resin (A) more. From the viewpoint of obtaining their balance, in resin composition and molded body, the total mass of the thermoplastic resin (A) relative to the total mass of the thermoplastic resin (A), natural fiber (B) and compatibilizer (C) ((A) / ((A)+(B)+(C))) is preferably 0.01 or more and 0.99 or less, more preferably 0.1 or more and 0.9 or less, more preferably 0.2 or more and 0.8 or less, more preferably 0.3 or more and 0.7 or less, particularly preferably 0.4 or more and 0.6 or less.
[0207] In addition, from the same point of view, in the resin composition and the molded product, the ratio of the total mass of the natural fiber (B) to the total mass of the thermoplastic resin (A), the natural fiber (B) and the compatibilizer (C) ((B) / ((A) + (B) + (C))) is preferably from 0.01 to 0.99, more preferably from 0.1 to 0.9, further preferably from 0.2 to 0.8, further preferably from 0.3 to 0.7, particularly preferably from 0.4 to 0.6, and extremely preferably from 0.52 to 0.6.
[0208] In addition, from the same viewpoint, in the resin composition and the molded body, the ratio of the total mass of the natural fiber (B) to the total mass of the thermoplastic resin (A) and the natural fiber (B) ((B) / ((A)+B))) is preferably 0.40 or more, more preferably 0.50 or more, further preferably 0.51 or more, and particularly preferably 0.52 or more. The upper limit value is not particularly limited, for example, it may be 1.00 or less, 0.90 or less, or 0.80 or less. That is, ((B) / ((A)+(B))) is preferably 0.40 or more and 1.00 or less, more preferably 0.50 or more and 0.90 or less, further preferably 0.51 or more and 0.90 or less, and particularly preferably 0.52 or more and 0.80 or less.
[0209] In addition, from the viewpoint of improving the processability of the resin composition, in the resin composition and the molded body, the ratio of the total mass of the processing aid (D) to the total mass (W) of the resin composition ((D) / (W)) is preferably from 0.01 to 0.99, more preferably from 0.02 to 0.9, and even more preferably from 0.05 to 0.8.
[0210] 2. Method for producing resin composition
[0211] The above-mentioned resin composition can be produced by melt-kneading the thermoplastic resin (A) and the natural fiber (B).
[0212] 2-1. Melt mixing
[0213] The melt kneading is performed by kneading the thermoplastic resin (A) and the natural fiber (B), the compatibilizer (C), the processing aid (D) and other components while heating them. By performing the melt kneading in the presence of water, a molded product having the above-mentioned properties can be obtained.
[0214] As the above-mentioned thermoplastic resin (A) and natural fiber (B), as well as compatibilizer (C), processing aid (D) and other components, the above-mentioned materials can be used. It should be noted that the natural fiber (B) is preferably in powder form, but can also be in fiber shape or paper shape. The average particle size of the natural fiber (B) in powder form is not particularly limited, but from the viewpoint of improving the mechanical strength and impact resistance of the molded body, it is preferably 5 μm or more, more preferably 7 μm or more, and further preferably 15 μm or more. In addition, from the same viewpoint, the average particle size of the natural fiber (B) is preferably 500 μm or less, more preferably 100 μm or less, and further preferably 60 μm or less. The average particle size of the natural fiber (B) is preferably 5 μm or more and 500 μm or less, more preferably 7 μm or more and 100 μm or less, further preferably 7 μm or more and 60 μm or less, and particularly preferably 15 μm or more and 60 μm or less.
[0215] Melt kneading may be performed at a temperature at which the thermoplastic resin (A) melts, specifically, at a temperature higher than the melting point of the thermoplastic resin (A). In addition, melt kneading may be performed at a temperature at which the natural fiber (B) does not undergo denaturation, that is, at a temperature at which no significant coloring, burning, or carbonization occurs in the natural fiber (B). Specifically, melt kneading is preferably performed at 110° C. to 280° C., more preferably, at 130° C. to 220° C.
[0216] In the present embodiment, it is considered that by melt-kneading in the presence of water, the natural fiber (B) is broken from the state of being agglomerated before kneading as the thermoplastic resin (A) is dissolved by utilizing the load of shear force and the action of hot water (including the physical action and chemical action (hydrolysis action) generated by hot water). In addition, by utilizing the load of shear force and the action of hot water, each natural fiber (B) is released from the network-like twisting of the natural fibers (B) and the shape is changed from a paper shape to a fibrous shape. By utilizing these actions, the natural fiber (B) can be dispersed in the thermoplastic resin (A) more uniformly than before.
[0217] In addition, melt kneading is preferably carried out in the presence of water in a subcritical state. The so-called "water in a subcritical state" is water in a high-temperature and high-pressure state that has not reached the critical point of water (temperature 374°C and pressure 22MPa). More specifically, it is a state in which the temperature is above the boiling point (100°C) of water at atmospheric pressure and below the critical point of water, and the pressure is at least near the saturated water vapor pressure. Water in a subcritical state has a larger ion product than water under atmospheric pressure at a temperature above 0°C and below 100°C. Therefore, it is inferred that the intermolecular bonds of the natural fiber (B) are weakened, further promoting the defibration of the natural fiber (B).
[0218] In this embodiment, preferably, a thermoplastic resin (A), a natural fiber (B), water, a compatibilizer (C), a processing aid (D) and other components are added to a closed container forming a closed space, and they are stirred vigorously. The temperature in the shell is heated to the above temperature by the heat generated by the above stirring, so that the thermoplastic resin (A) and other resin components are melted. It should be noted that the closed container preferably has an exhaust mechanism for preventing air from the outside from invading and discharging the water vapor generated by the above heat. In the closed space, the mixture is vigorously kneaded with water, thereby enabling melt kneading in the presence of water. On the other hand, by utilizing the above heating to convert the moisture into water vapor and discharging the water vapor to the outside, it is also possible to prevent residual water in the kneaded product (resin composition).
[0219] Natural fiber (B) is usually hygroscopic. In a common mixing method, the resin composition contains water. Therefore, the water that cannot be discharged from the extruder is retained as water vapor. As a result, the composition ratio of natural fiber to resin is unstable, and the mechanical strength is sometimes unstable. However, in the manufacturing method of the present invention, water can be efficiently discharged in the form of high-temperature steam during melt mixing, so the water content of the obtained resin composition can be fully reduced to a desired level.
[0220] The melt kneading in the above-mentioned closed space can be carried out using an intermittent closed kneading machine (such as the mixing and pulverizing device described in International Publication No. 2004 / 076044) having a cylindrical outer shell, a rotor with multiple stirring blades on the outer periphery, and an exhaust section for exhausting water vapor while maintaining the pressure of the outer shell.
[0221] The above-mentioned intermittent closed type kneading machine can determine the end time of melt kneading based on the measurement results obtained by using a thermometer and a pressure gauge installed in the housing, or can determine the end time of melt kneading based on the rotational torque of the rotor. For example, with regard to the stirring time, it is preferred to end the stirring within 30 seconds from the time when the torque rises to the maximum value and then decreases, and the torque change rate becomes less than 5% per 1 second.
[0222] 3. Molding
[0223] The resin composition can be formed into a film, plate, prism, column, or any other shape by extrusion molding, compression molding, injection molding, blow molding, transfer molding, cast molding, inflation molding, etc. Among them, it is preferably used for the production of injection molded products by injection molding.
[0224] 4. Purpose
[0225] The above-mentioned molded body can be used as, for example, outdoor fences of buildings, wooden decks, flower racks (grape racks), grilles and other external components, inner wall materials, floor materials, ceiling materials, furniture materials and other internal components, other amusement equipment, etc.
[0226] In addition, the molded article can also be used as a shock absorbing member. Examples of the shock absorbing member include health products, care products (e.g., fall prevention films, felts, sheets), shock absorbing pads, protection and protective equipment (e.g., helmets, shields), sports products (e.g., sports grips), sports protective gear, rackets, balls, transport tools (e.g., transport shock absorbing grips, shock absorbing sheets), industrial materials (e.g., vibration-damping trays, shock absorbing shock absorbers, shock absorbing members for footwear, shock absorbing foams, shock absorbing films), and shock absorbing members for automobiles (e.g., bumper shock absorbing members, buffer members), etc.
[0227] In addition, the molded article can also be used for automotive interior decorative members such as instrument panels, inter-seat control boxes, dashboards, door lock bezels, steering wheels, power window switch bases, center clusters, dashboards, roof linings, cowl side trims, door trim substrates, deck trims, inner panels, pillar garnishes, rear packages, package trays, switch seats, rear quarter panels, seat structural materials, seat back panels, core materials for armrests, ceiling substrates, wall materials, floor materials, impact absorbing materials, and sound absorbing materials; and automotive interior decorative members such as sealing strips, bumpers, bumper bumper blocks, side mud guards, body panels, fairings, fenders, spoilers, air outlet grilles, pressure relief covers, wheel covers, center pillars, door mirrors, center ornaments, side malls, door malls, and window strips. The products include: automotive exterior decoration components such as doors, windows, headlight covers, taillight covers, and windshield parts; various front panels of AV equipment; surface decoration materials such as buttons and badges; various parts such as housings, display windows, and buttons of mobile phones; exterior decoration materials for furniture; interior decoration materials for buildings such as walls, ceilings, and floors; exterior decoration materials for buildings such as siding, walls, roofs, doors, and windshields; surface decoration materials for furniture such as window frames, door leaves, railings, thresholds, and door lintels; optical components such as various displays, lenses, mirrors, goggles, and window glass; interior and exterior decoration components for various means of transportation other than automobiles such as trams, aircraft, and ships; and various packaging containers such as bottles, cosmetic containers, and storage boxes, packaging materials, souvenirs, small items, and other miscellaneous goods.
[0228] The molded article can be preferably used in many fields such as electrical insulating materials, industrial component materials, building materials, leisure parts, agricultural tool parts, marine or fishing tool parts, etc. In particular, the present invention can be applied to baseboards, surface decorative boards, door materials, exterior wall materials, washstands, counter materials, foundation receiving boards, window frames, wall materials, cornice wood, railings, handles, structural materials, civil timber, columns, niche columns, decorative columns, earthquake-resistant materials, wallpaper, door and window partition ceiling materials, base materials, tatami, floors, concrete panels, bracket materials, shielding boards, sound insulation boards, box ceilings of furniture, door panels, front and back panels, shelf panels, sleeve plates, curtain panels, decks, backrest panels, seat panels, kitchen components, waterproof materials, mildew-proof materials, anti-corrosion materials, window guards, cover panels, skirt panels, side panels, bath equipment, floor pans, bathroom ceilings, bathroom walls, bathtubs, buckets, sanitary ware, toilet seats, toilet lids, home appliances, radio television receivers, etc. receiver), cabinets, audio cabinets, amplifier cabinets, speakers, speaker boxes, piano organ motherboards, large roofs, curved roofs, upper and lower winding plates, buoyancy bodies (foaming) of life jackets, surfboards, cold-proof glove materials, fishing supplies (floats, decorative balls, fishing balls, baits), camping supplies, agricultural films, gardening pillars, plastic greenhouse pillars or pillar fixing fasteners, offshore fenders, floats, etc.
[0229] In addition, the above-mentioned molded body can also be used for small mobile mechanisms represented by bicycles and electric power-assisted bicycles, escalators, elevators, etc., aviation materials represented by manned aircraft, unmanned aircraft, supersonic passenger aircraft, rockets, and artificial satellites, mobile mechanisms such as fuel cell vehicles, hydrogen battery vehicles, and magnetic levitation trains, various amusement equipment, various components of robots, signal devices, wires, water pipes, air pipes, various infrastructure represented by optical fibers, liquid crystal panels, solar cells, antennas, transistors, OA equipment interior decoration, OA equipment housing, toilet lighting fixtures, umbrellas, raincoats, insulation materials, pedals, coatings, barriers, hydrophilic and hydrophobic control agents, papermaking materials, tires, shock absorbers, hoses, various rubber materials such as vibration-proof rubber, food and beverage containers, materials for 3D printers, agricultural films, liquid filters, air filters, semiconductor filters, various non-woven fabric materials, musical instruments, audio materials, wigs, wig covers, clocks, tombstones, glasses, sunglasses, wearable terminals, etc.
[0230] Example
[0231] Hereinafter, the present invention will be described with reference to Examples. However, the scope of the present invention is not to be limitedly interpreted based on these Examples.
[0232] In addition, in the following experiments, the physical properties of each resin were measured by the following methods.
[0233] 1. Preparation of Materials
[0234] 1-1. Preparation of thermoplastic resin (A-1)
[0235] As the thermoplastic resin (A-1), Prime Polypro (trade name) Grade J137G (polypropylene) manufactured by Prime Polymer Co., Ltd. was used.
[0236] 1-2-1. Preparation of natural fiber (B-1)
[0237] As the natural fiber (B-1), KC FLOCK (trade name) Grade W-50GK (powdered cellulose) manufactured by Nippon Paper Industries, Ltd. (apparent specific gravity: 0.23 g / ml to 0.33 g / ml, average particle size: about 45 μm) was used.
[0238] 1-2-2. Preparation of natural fiber (B-2)
[0239] As the natural fiber (B-2), KC FLOCK (trade name) Grade W-100GK (powdered cellulose) manufactured by Nippon Paper Industries, Ltd. (apparent specific gravity: 0.30 g / ml to 0.40 g / ml, average particle size: about 37 μm) was used.
[0240] 1-3-1. Synthesis of compatibilizer (C-1)
[0241] 200 g of propylene-ethylene copolymer (ethylene content: 2.5% by mass, MFR: 40 g / 10 min) was placed in a stainless steel thermal decomposition device (content: 1.5 L) equipped with a stirring device, a nitrogen introduction tube, and a condenser, and the system was fully substituted with nitrogen. Next, the thermal decomposition device was heated to 380° C. while nitrogen was flowing to melt the propylene-ethylene copolymer, and the propylene-ethylene copolymer was thermally decomposed for 2.5 hours under this condition. Then, the thermal decomposition device was cooled to room temperature to obtain a polypropylene wax. 500 g of the polypropylene wax was placed in a glass reactor and heated to 170° C. under a nitrogen atmosphere to melt it. Next, 26 g of maleic anhydride and 5.5 g of di-tert-butyl peroxide were continuously supplied to the reactor over 3 hours. Then, the contents of the reactor were subjected to a heating reaction for 1 hour. The contents of the reactor were degassed for 0.5 hours in a vacuum of 10 mmHg while being kept in a molten state to remove volatile components, and then cooled to obtain a compatibilizer (C-1) which was an acid-modified polypropylene wax.
[0242] 1-3-2. Synthesis of compatibilizer (C-2)
[0243] 1 part by mass of Prime Polypro (trade name) Grade F327 (polypropylene) manufactured by Prime Polymer Co., Ltd., 1 part by mass of maleic anhydride (manufactured by Wako Pure Chemical Industries, Ltd.) and 0.25 parts by mass of 2,5-dimethyl-2,5-bis(tert-butylperoxy)hex-3-yne (manufactured by NOF Corporation, trade name Perhexyne 25B) were mixed, and the mixture was extruded using a twin-screw kneader (manufactured by The Nippon Steel Works, Ltd., TEX-30, L / D=40, using a vacuum exhaust port) at a cylinder temperature of 220° C., a screw speed of 200 rpm, and a discharge amount of 80 g / min to obtain a compatibilizer (C-2) which is an acid-modified polypropylene resin composition containing maleic acid-modified polypropylene and unreacted maleic anhydride. The obtained compatibilizer (C-2) was dissolved in xylene and purified by reprecipitation in acetone. The graft amount of maleic anhydride was measured by IR and found to be 0.7% by mass. The number average molecular weight (Mn) was measured by GPC and found to be 28,000.
[0244] 1-3-3. Synthesis of compatibilizer (C-3)
[0245] In the production of the maleic acid-modified polypropylene (C-2), 100 parts by mass of Prime Polypro (trade name) Grade J106G manufactured by Prime Polymer Co., Ltd., 15 parts by mass of maleic anhydride, and 2.5 parts by mass of dicumyl peroxide (manufactured by NOF Corporation, trade name Percumyl D) were mixed and reacted in a toluene solution for 5 hours. The same operation as the synthesis of the compatibilizer (C-2) was performed to obtain a compatibilizer (C-3) as an acid-modified polypropylene resin composition containing maleic acid-modified polypropylene and unreacted maleic anhydride. The obtained compatibilizer (C-3) was dissolved in xylene, reprecipitated in acetone to be purified, and the grafting amount of maleic anhydride was measured by IR, and the result was 2.8% by mass. The number average molecular weight (Mn) was measured by GPC, and the result was Mn was 18,000.
[0246] 1-4. Preparation of processing aid (D-1)
[0247] As the processing aid (D-1), an olefin resin C-4 described in Examples of JP-A-2010-150436 was used.
[0248] 2. Preparation of resin composition
[0249] 2-1. Resin composition 1
[0250] Thermoplastic resin (A-1) and natural fiber (B-1) were prepared at a mass ratio of 45:55 (total mass: 4 kg).
[0251] 4 kg of water was added to the natural fiber (B-1) prepared above, and mixed until the whole was fused. The mixture and the thermoplastic resin (A-1) were put into an intermittent closed kneading device (MF type mixing and melting device, model: MF5000R / L, manufactured by Discharge Precision Machining Laboratory Co., Ltd.) having a housing and a rotor with stirring blades, and the peripheral speed of the front end of the stirring blade was set to 40 m / sec, and high-speed stirring was performed to mix the materials.
[0252] When kneading is started, the rotational torque of the rotor rises to a maximum value, then decreases and the rate of change of the torque decreases. When the rate of change of the torque becomes less than 5% per second, the rotational torque becomes minimum, and kneading is continued for 7 seconds from the minimum time point to obtain resin composition 1.
[0253] 2-2. Resin composition 2 to resin composition 10
[0254] Resin compositions 2 to 10 were obtained in the same manner as in Example 1 except that the composition ratio was changed as described in Table 1 without changing the total mass of the materials put into the kneading device.
[0255] 2-3. Resin composition 11
[0256] Thermoplastic resin (A-1) and natural fiber (B-1) were prepared at a mass ratio of 49:51 (total mass: 4 kg).
[0257] These were heated and kneaded at 200° C. using a twin-screw kneading extruder (TEX-30, L / D=40, manufactured by The Nippon Steel Works, Ltd.) to obtain a resin composition 11.
[0258] 3. Evaluation
[0259] 3-1. Preparation of test pieces for measurement
[0260] Resin compositions 1 to 11 were dried at 80° C. for 15 hours, respectively. Then, injection molding was performed using an injection molding machine equipped with a JIS 7162-1B dumbbell test piece mold (thickness 4 mm) at a molding temperature of 180° C. and a mold temperature of 80° C. to obtain test pieces for measurement from resin compositions 1 to 11, respectively.
[0261] The following measurements were performed on the test piece for measurement.
[0262] In addition, for resin compositions 5, 9 and 11, the average fiber length and maximum fiber length of the natural fibers (B) of resin compositions 5, 9 and 11, as well as the average size, number and area (%) of the natural fibers (B) were measured without processing them into test pieces for measurement.
[0263] 3-2. Average fiber length and maximum fiber length of natural fibers (B)
[0264] An arbitrary part of the test piece for physical property measurement was cut into 1mm×1mm×2mm, and X-ray CT was taken with a field of view of about 3mm×3mm. The measurement device used a high-resolution 3D X-ray microscope nano3DX (manufactured by Rigaku Corporation), and CT measurement was performed using low-energy, high-brightness X-rays that can obtain contrast even for light elements. The detailed measurement conditions are as follows.
[0265]
[0266] Using the obtained X-ray CT image, the fiber length of the natural fiber was measured at a pitch of 10 μm in a range of 1,000×1,000×1,000 voxel, and the average fiber length of the natural fiber (B) was taken, and the maximum value in the fiber length distribution was taken as the maximum fiber length.
[0267] The X-ray CT image of the injection molded product obtained from the resin composition 1 is shown in FIG. Figure 1 .
[0268] 3-3. Average size, number, and area of natural fibers (B) (%)
[0269] A cross section (TD cross section) perpendicular to the flow direction of the resin during injection molding was cut from the test piece for measurement. The TD cross section was observed by magnifying it to 75 times in the range of 1.8 mm × 1.2 mm using a high-resolution scanning microscope (SEM) at a working distance of 6.5 mm. The area filled with natural fibers (B) in the enlarged image obtained by observation was painted black and the other areas were painted white to prepare a secondary image. The obtained secondary image was read into the image analysis software (ImageJ), and the commands: Process, Binary, Make Binary were executed to perform binary image processing. The average size of natural fibers (B) in the area of the observation field (Average Size of black area), the number of natural fibers (B) (Count of black area), and the area % of natural fibers (B) (Area Fraction of black area) were calculated by the commands: Analyze, Analyze Particles.
[0270] The SEM images of the TD cross sections of the injection molded articles obtained from the resin composition 1 are shown in Figure 2 A, will be Figure 2 The secondary image obtained by A is shown in Figure 2 B.
[0271] 3-4. Charpy impact strength
[0272] A Charpy impact test at room temperature was performed in accordance with JIS K 7111-2 (2006) using a test piece of 10 mm (width)×4 mm (thickness)×80 mm (length) cut out from the test piece for measurement.
[0273] 3-5. Bending test (bending strength, bending elastic modulus)
[0274] In accordance with JIS K 7171 (2022), the flexural strength and flexural modulus were measured under the conditions of a load range of 200 N, a test speed of 2 mm / min, and a bending span of 64 mm.
[0275] 3-6. Tensile test (tensile strength, tensile elastic modulus)
[0276] According to JIS K 7161-2 (2014), the tensile strength and tensile modulus were measured under the conditions of a load range of 2 kN and a test speed of 50 mm / min.
[0277] 3-7. Appearance quality (sensory evaluation)
[0278] Five researchers who had worked on the resin composition were recruited as sensory testers. The resin composition was placed on a smooth workbench, and black-painted paper and white-painted paper were placed next to it. Then, white was scored as 0 points and black was scored as 10 points. The sensory testers visually inspected the surface appearance of the resin composition and evaluated the surface color score between 0 and 10 points. Then, the scores of the five sensory testers were averaged and evaluated as the appearance quality. It should be noted that the lower the score, the better the appearance quality can be evaluated.
[0279] 4. Results
[0280] The compositions and evaluation results of resin compositions 1 to 12 are shown in Tables 1 and 2. It should be noted that for resin compositions 5, 9, and 11, the measurement results of the test pieces for measurement are shown as 5-1, 9-1, and 11-1, respectively, and the measurement results of the unprocessed resin compositions are shown as 5-2, 9-2, and 11-2. In addition, the SEM image of resin composition 2 is shown in Figure 3 .
[0281] [Table 1]
[0282]
[0283] [Table 2]
[0284]
[0285] It can be confirmed from Tables 1 and 2 that an injection molded article comprising a thermoplastic resin (A) and a natural fiber (B), wherein the average fiber length of the natural fiber (B) photographed and measured by X-ray computed tomography (X-ray CT) is 32 μm or more, and the ratio (number / average size) of the number of the natural fibers (B) to the average size (μm) of the natural fibers (B) in an image obtained by photographing and measuring a cross section along the TD direction with a scanning electron microscope (SEM) at a working distance of 6.5 mm and a magnification of 75 times over a range of 1.8 mm×1.2 mm is 400 or more, has superior mechanical strength compared to an injection molded article that does not have such a ratio.
[0286] In addition, it can be confirmed from Tables 1 and 2 that the fiber length and distribution characteristics (average fiber length, maximum fiber length, average size, number, and area) of the natural fiber (B) do not change significantly before and after injection molding.
[0287] In addition, if Figure 3 As shown, when a compatibilizer is used, the thermoplastic resin (A) and the natural fiber (B) are closely bonded.
[0288] This application claims the priority of Japanese Patent Application No. 2022-149291 filed on September 20, 2022. The matters described in the specification, claims, and drawings of the original application of this application are incorporated into this application by reference.
[0289] Industrial Applicability
[0290] The resin composition of the present invention can obtain a molded body having excellent mechanical strength compared to the conventional resin composition in which natural fibers are dispersed in the resin. Therefore, it can be expected that the present invention can expand the possibility of application of the resin composition of the resin containing the natural fibers to various uses, and contribute to the further popularization of such resin composition.
Claims
1. A resin composition comprising: Thermoplastic resin (A), and Natural fiber (B), The average fiber length of the natural fiber (B), measured by photographing the resin composition using X-ray computed tomography (X-ray CT), is 32 μm or longer. The ratio (number / average size) of the number of the natural fibers (B) in the image obtained by photographing and measuring a cross section along the TD direction of the resin composition at a working distance of 6.5 mm and a magnification of 75 times over a range of 1.8 mm×1.2 mm is 400 or more.
2. The resin composition according to claim 1, wherein For the resin composition, the ratio (number / area) of the number of the natural fibers (B) in the image obtained by photographing and measuring the cross section along the TD direction using SEM, in which the range of 1.8 mm×1.2 mm was photographed at a working distance of 6.5 mm and a magnification of 75 times, relative to the area (%) occupied by the natural fibers (B) is 700 or more.
3. The resin composition according to claim 1 or 2, wherein The ratio ((B) / (A)) of the total mass of the natural fiber (B) to the total mass of the thermoplastic resin (A) is 0.01 to 10.
4. The resin composition according to claim 1 or 2, wherein The ratio of the total mass of the natural fiber (B) to the total mass of the thermoplastic resin (A) and the natural fiber (B) ((B) / ((A)+(B))) is 0.50 or more. 5 . The resin composition according to claim 1 , comprising a compatibilizer (C), wherein the compatibilizer (C) comprises a modified polyolefin (C1).
6. The resin composition according to claim 5, wherein The modified polyolefin (C1) is an acid-modified polyolefin resin composition.
7. The resin composition according to claim 5, wherein The ratio of the total mass of the compatibilizer (C) to the total mass of the thermoplastic resin (A), the natural fiber (B) and the compatibilizer (C) ((C) / ((A)+(B)+(C))) is 0.008 to 0.
1. 8 . The resin composition according to claim 1 , comprising a processing aid (D), wherein the processing aid (D) comprises a polyolefin wax (D1).
9. The resin composition according to claim 1 or 2, wherein The natural fibers (B) include cellulose fibers.
10. The resin composition according to claim 9, wherein The maximum fiber length of the natural fiber (B), measured by photographing the resin composition using X-ray computed tomography (X-ray CT), is 900 μm or less.
11. The resin composition according to claim 1 or 2, wherein The thermoplastic resin (A) contains polyolefin.
12. The resin composition according to claim 1 or 2, wherein The ratio ((A) / (W)) of the total mass of the thermoplastic resin (A) to the total mass (W) of the resin composition is 0.5 or less.
13. A molded article formed by injection molding the resin composition according to claim 1 or 2.
14. The method for producing a resin composition according to claim 1 or 2, wherein: The thermoplastic resin (A) and the natural fiber (B) are melt-kneaded using a batch-type closed kneading device having a housing and a rotor with stirring blades, and The melt kneading is performed by heating the temperature inside the housing to a temperature at which the natural fibers (B) are not denatured by the rotation of the rotor in the presence of water.
Citation Information
Patent Citations
Production of ethylenic wax
JP1996239414A
Game machine
JP2005028187A
Olefin resin-based coating material
JP2010150436A
Cellulose composites containing wood pulp
JP2019512591A
Joint heat insulation cover and manufacturing method therefor
JP2022149291A